Electrostatic charge image development toner, method of manufacturing electrostatic charge image development toner, electrostatic charge image developer, toner cartridge, process cartridge, and image forming device
By forming a multi-layer amorphous resin layer on the large-diameter particle toner and containing an outer layer of the release agent, the problem of fine lines and gloss in the toner for electrostatic development is solved, and high-quality image reproduction is achieved.
Patent Information
- Application Number
- JP2024200920
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2041-05-21
AI Technical Summary
When it is difficult to prepare electrostatic development toners using large diameter particles, it is difficult to achieve image reproduction of thin lines and high gloss.
Toner particles with a multi-layer structure are adopted, in which the core particles are composed of particles larger than 1 μm, the outer layer is coated with two or more amorphous resin layers, and the outer layer contains a release agent, ensuring good adhesion through multiple resin layer formation processes.
The thin line reproduction ability and gloss of toners are improved, and the unevenness caused by particle aggregation is reduced, thereby achieving high-quality electrostatic development images.
Smart Images

Figure 2025015746000003 
Figure 2025015746000004 
Figure 2025015746000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a toner for developing electrostatic images, a method for producing a toner for developing electrostatic images, an electrostatic image developer, a toner cartridge, a process cartridge, and an image forming apparatus. [Background technology]
[0002] Patent Document 1 discloses an electrostatic latent image developing toner including a plurality of toner particles each including a core containing a binder resin and a release agent, and a multilayered shell layer partially covering the surface of the core, the multilayered shell layer including a first shell layer containing a first polymer including a repeating unit having an oxazoline group, a second shell layer containing a second polymer including a repeating unit having a carboxyl group, and a third shell layer containing a third polymer including a repeating unit having an oxazoline group, the first shell layer, the second shell layer, and the third shell layer having a laminated structure in the order of the first shell layer, the second shell layer, and the third shell layer from the core side, and the second shell layer is in contact with an area of the surface region of the core that is not covered by the first shell layer.
[0003] Patent Document 2 discloses a toner for developing electrostatic images, which is composed of toner particles having a multilayer structure in which an intermediate layer is formed on the surface of a core particle and a shell layer is laminated on the intermediate layer, and the core particle is composed of a matrix phase made of a vinyl polymer A in which a crystalline polyester resin is dispersed as a domain phase, the average diameter of the domain phase being 300 nm or less, the intermediate layer contains a vinyl polymer B, and the shell layer contains an amorphous resin in which a vinyl polymer segment and a polyester polymer segment are chemically bonded to each other.
[0004] Patent Document 3 discloses a toner for developing electrostatic latent images having a core-shell structure in which core particles containing at least a resin and a colorant are coated with a shell layer, the shell layer being free of wax, and the difference (ΔSP) between the solubility parameter values (SP values) of the core particle and the shell layer being 0.2 to 0.7. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2018-097052 A [Patent Document 2] JP 2014-206610 A [Patent Document 3] JP 2009-163026 A Summary of the Invention [Problem to be solved by the invention]
[0006] In recent years, there has been an increasing demand for anti-counterfeiting technology, such as printing using "special colors" on coupons, discount vouchers, certificates, etc., and printing lines, illustrations, etc. by arranging minute micro-characters that are unreadable to the naked eye. However, when a toner containing large particles such as scaly pigments or large-diameter luminescent particles as a coloring material for a special color is used, it is difficult to obtain good electrical properties and powder flowability, and it may be difficult to obtain fine line reproduction.
[0007] The present invention aims to provide a toner for developing electrostatic images, which contains toner particles having a shell layer and core particles which are large particles having a number-average particle size of 1 μm or more, and which has high fine line reproducibility compared to a case in which the shell layer is made of only one resin layer or a case in which the shell layer is made of two or more resin layers and the outermost layer contains a release agent. [Means for solving the problem]
[0008] Specific means for solving the above problems include the following aspects.
[0009] <1> Core particles having a number average particle size of 1 μm or more; a shell layer which is composed of two or more resin layers containing an amorphous resin and covers a surface of the core particle, the shell layer being an outermost layer of the two or more resin layers which is composed of the amorphous resin; A toner for developing electrostatic images, comprising toner particles having the formula: <2> The shell layer is composed of three or more resin layers containing an amorphous resin, an innermost layer of the three or more resin layers is a resin layer made of the amorphous resin; An intermediate layer, which is a layer other than the outermost layer and the innermost layer among the three or more resin layers, includes a resin layer containing the amorphous resin and at least one selected from the group consisting of a release agent, a crystalline resin, and a colorant. <1> 2. The toner for developing electrostatic images according to claim 1 .
[0010] <3> The large particles include scaly particles. <1> or <2> 2. The toner for developing electrostatic images according to claim 1 . <4> The large particles include luminescent particles. <1> or <2> 2. The toner for developing electrostatic images according to claim 1 . <5> One of the core particles is composed of one of the large diameter particles. <1> ~ <4> 10. The toner for developing an electrostatic image according to claim 9, <6> One of the core particles contains two or more of the large particles and an amorphous resin. <1> ~ <4> 10. The toner for developing an electrostatic image according to claim 9, <7> The content of the large diameter particles relative to the total amount of the core particles is 50% by mass or more. <6> 2. The toner for developing electrostatic images according to claim 1 . <8> the toner contains no resin particles alone that contain an amorphous resin and do not contain the large-diameter particles, or the content of the resin particles alone is 80% by number or less of the entire toner for developing electrostatic images; <1> ~ <7> 10. The toner for developing an electrostatic image according to claim 9,
[0011] <9> a core particle dispersion preparation step of preparing a core particle dispersion in which core particles having a number average particle size of 1 μm or more are dispersed; a resin particle layer forming step of adding amorphous resin particles to the core particle dispersion and aggregating the amorphous resin particles so as to adhere to the core particles, thereby forming a resin particle layer on the surfaces of the core particles; a repeating step of repeating the above operation one or more times, in which the particles added in the final step are only the amorphous resin particles, thereby forming aggregated particles having two or more resin particle layers on the surface of the core particle, the outermost layer of which is made of the amorphous resin particles; a fusion / coalescence process in which the aggregated particle dispersion liquid in which the aggregated particles are dispersed is heated to fuse and coalesce the aggregated particles to form toner particles; A method for producing a toner for developing an electrostatic image comprising the steps of: <10> the particles added in the resin particle layer forming step are the amorphous resin particles alone, The repeating step is a step of repeating the above operation two or more times, and the particles added in one or more of the operations excluding the last one contain the amorphous resin particles and at least one kind selected from the group consisting of release agent particles, crystalline resin particles, and colorant particles, thereby forming aggregated particles having three or more resin particle layers on the surface of the core particle, the innermost layer of the three or more resin particle layers being made of the amorphous resin particles, and an intermediate layer, which is a layer other than the outermost layer and the innermost layer of the three or more resin particle layers, containing the amorphous resin particles and at least one kind selected from the group consisting of the release agent particles, the crystalline resin particles, and the colorant particles. <9> 2. A method for producing the toner for developing electrostatic images according to claim 1 .
[0012] <11> The large-diameter particles include at least one type selected from the group consisting of scale-like particles and luminescent particles. <9> or <10> 2. A method for producing the toner for developing electrostatic images according to claim 1 . <12> One of the core particles is composed of one of the large diameter particles. <9> ~ <11> 13. A method for producing the toner for developing electrostatic images according to claim 12. <13> One of the core particles contains two or more of the large particles and an amorphous resin. <9> ~ <12> 13. A method for producing the toner for developing electrostatic images according to claim 12. <14> The content of the large diameter particles relative to the total amount of the core particles is 50% by mass or more. <13> 2. A method for producing the toner for developing electrostatic images according to claim 1 .
[0013] <15> In all operations of the resin particle layer forming step and the repeating step, a flocculant is added to the core particle dispersion in addition to the amorphous resin particles. <9> ~ <14> 13. The method for producing the toner for developing electrostatic images according to claim 12. <16> the aggregation temperature in each operation of the repeating step is higher than the aggregation temperature in the immediately preceding operation; <9> ~ <15> 13. A method for producing the toner for developing electrostatic images according to claim 12. <17> the amount of the amorphous resin particles added in each operation of the repeating step is greater than the amount of the amorphous resin particles added in the immediately preceding operation; <9> ~ <16> 13. A method for producing the toner for developing electrostatic images according to claim 12.
[0014] <18> <9> ~ <17> 13. A toner for developing electrostatic images, which is obtained by the method for producing a toner for developing electrostatic images according to claim 12.
[0015] <19> <1> ~ <8> and <18> 2. An electrostatic image developer comprising the toner for developing electrostatic images according to claim 1. <20> <1> ~ <8> and <18> The toner for developing an electrostatic image according to any one of claims 1 to 4 is contained in the container. A toner cartridge that is detachably attached to an image forming apparatus. <21> <19> and a developing unit which develops an electrostatic image formed on a surface of an image carrier into a toner image by using the electrostatic image developer, A process cartridge that is detachably attached to an image forming apparatus. <22> An image carrier; a charging means for charging the surface of the image carrier; an electrostatic image forming means for forming an electrostatic image on the charged surface of the image carrier; <19> a developing means for developing the electrostatic image formed on the surface of the image carrier into a toner image by using the electrostatic image developer; a transfer means for transferring the toner image formed on the surface of the image carrier to a surface of a recording medium; a fixing means for fixing the toner image transferred onto the surface of the recording medium; An image forming apparatus comprising: Effect of the Invention
[0016] <1> According to the present invention, there is provided a toner for developing electrostatic images which includes toner particles having a shell layer and core particles which are large-diameter particles with a number-average particle size of 1 μm or more, and which has high fine-line reproducibility compared to a case in which the shell layer is made of only one resin layer or a case in which the shell layer is made of two or more resin layers and the outermost layer contains a release agent. <2> According to the invention related to the above, there is provided a toner for developing electrostatic images which has high fine line reproducibility compared to a toner in which the innermost layer contains a release agent.
[0017] <3> According to the present invention, even if the large diameter particles contain scaly particles, an electrostatic image developing toner having high fine line reproducibility is provided, compared to a case in which the shell layer consists of only one resin layer or a case in which the shell layer consists of two or more resin layers and the outermost layer contains a release agent. <4> According to the present invention, even if the large diameter particles contain luminescent particles, a toner for developing electrostatic images is provided which has high fine line reproducibility compared to a case in which the shell layer consists of only one resin layer or a case in which the shell layer consists of two or more resin layers and the outermost layer contains a release agent. <5> According to the present invention, there is provided a toner for developing electrostatic images in which the function of the large diameter particles is more easily exhibited than when one core particle contains two or more large diameter particles and an amorphous resin. <6> According to the invention related to the above, there is provided a toner for developing electrostatic images which provides a toner-fixed image with better smoothness than when one core particle is composed of one large particle. <7> According to the invention, there is provided a toner for developing electrostatic images in which the functions of the large diameter particles are more easily exhibited than when the content of the large diameter particles is less than 50% by mass. <8> According to the present invention, there is provided a toner for developing electrostatic images which can provide fixed images with better graininess than when the content of resin particles alone exceeds 80% by number.
[0018] <9> , <11> , <12> , <13> or <14> According to the present invention, there is provided a method for producing a toner for developing electrostatic images, which does not have a repeating process and can produce a toner for developing electrostatic images with high fine line reproducibility compared to a case in which a resin particle layer is formed only once. <10> According to the present invention, there is provided a method for producing a toner for developing an electrostatic image, which can obtain a toner for developing an electrostatic image with excellent thin line reproducibility compared to a case where the innermost layer of the resin particle layer contains a release agent. <15> According to the present invention, there is provided a method for producing a toner for developing an electrostatic image, which can obtain a toner for developing an electrostatic image with excellent thin line reproducibility compared to when a coagulant is not added in the repeating step. <16> According to the present invention, there is provided a method for producing a toner for developing electrostatic images, which can produce a toner for developing electrostatic images with high fine line reproducibility, compared to a case in which the aggregation temperature in the repeated step is equal to or lower than the aggregation temperature in the immediately preceding operation. <17> According to the present invention, there is provided a method for producing a toner for developing electrostatic images, which can produce a toner for developing electrostatic images with excellent thin line reproducibility, compared to a case in which the amount of amorphous resin particles added in the repeated step is equal to or less than the amount of amorphous resin particles added in the immediately preceding operation.
[0019] <18> According to the invention, there is provided a toner for developing electrostatic images having high fine line reproducibility compared to a case where a resin particle layer is formed only once without a repeating process.
[0020] <19> , <20> , <21> or <22> According to the invention, there is provided an electrostatic image developer, a toner cartridge, a process cartridge, or an image forming apparatus, which includes a toner for developing electrostatic images having high fine line reproducibility compared to a toner containing toner particles having a shell layer and core particles with a number average particle diameter of 1 μm or more, wherein the shell layer is made of only one resin layer, or a shell layer is made of two or more resin layers and the outermost layer contains a release agent, or a resin particle layer is formed only once without a repeating process. [Brief description of the drawings]
[0021] [Figure 1] 1 is a schematic diagram illustrating an image forming apparatus according to an embodiment of the present invention; [Diagram 2] FIG. 2 is a schematic diagram illustrating a process cartridge according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Hereinafter, an embodiment of the present invention will be described as an example. The description and examples are merely illustrative of the embodiment, and are not intended to limit the scope of the present invention. In the present specification, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range. In addition, in the present specification, the upper or lower limit of the numerical range may be replaced with a value shown in the examples.
[0023] Each component may contain multiple types of the corresponding substance. When referring to the amount of each component in a composition, if the composition contains multiple substances corresponding to each component, the amount refers to the total amount of those multiple substances present in the composition, unless otherwise specified.
[0024] [Toner for developing electrostatic images] The toner for developing electrostatic images according to the present embodiment (hereinafter, the toner for developing electrostatic images is also referred to as "toner") includes toner particles having a core particle having a large diameter particle (hereinafter, sometimes simply referred to as "large diameter particle") with a number average particle diameter of 1 μm or more, and a shell layer that is made of two or more resin layers containing an amorphous resin and covers the surface of the core particle. The shell layer includes a resin layer made of an amorphous resin as the outermost layer of the two or more resin layers. The toner according to the present embodiment has the above-described composition, and thus has high thin line reproducibility. The reason for this is presumed to be as follows.
[0025] When a resin layer is formed by adhering amorphous resin particles to core particles having a large diameter with a number average particle size of 1 μm or more, the amorphous resin particles may be difficult to adhere to the surfaces of the core particles. In particular, when the core particles have large diameter particles, it is required to attach more resin than when the core particles do not have large diameter particles. Therefore, for example, when amorphous resin particles are added to a dispersion of core particles, the concentration of amorphous resin particles in the dispersion increases due to the addition of many amorphous resin particles, and the amorphous resin particles tend to aggregate with each other. Then, resin particles alone that do not contain core particles are formed, and toner particles in which the surface of the core particles is not completely covered with the resin layer and exposed may be formed. Since toner particles in which the surface of the core particles is exposed have low charging properties, if there is a variation in the coverage rate of the resin layer on the surface of the core particles, the charging distribution becomes wide, toner scattering occurs, and thin line reproducibility may decrease (for example, microcharacters may be crushed, etc.).
[0026] In contrast to this, the present embodiment has a shell layer made up of two or more resin layers, and the outermost layer of the shell layer is made of an amorphous resin. That is, the toner particles in this embodiment are obtained by coating the core particles with a resin layer through two or more steps. For example, when a resin layer is formed on the surface of the core particles by adding amorphous resin particles to a dispersion of the core particles, the concentration of the amorphous resin particles in the dispersion is lowered by going through two or more steps compared to the case where the same mass of the resin layer is formed on the surface of the core particles in one step. Therefore, it is considered that the adhesion of the amorphous resin particles to the surface of the core particles is more likely to occur than the aggregation of the amorphous resin particles, thereby suppressing the formation of resin particles alone, and increasing the coverage of the resin layer on the surface of the core particles. And, the high coverage of the resin layer on the surface of the core particles suppresses the decrease in chargeability caused by the exposure of the surface of the core particles, thereby improving the thin line reproducibility.
[0027] On the other hand, even if the toner has a shell layer composed of two or more resin layers, if the outermost shell layer contains a release agent, the toner particles may aggregate, the particle size distribution may become broad, and the electrical properties may vary, resulting in a decrease in fine line reproducibility. Similarly, if the outermost shell layer contains a crystalline resin, the toner particles may aggregate, resulting in a decrease in fine line reproducibility. In contrast, in the present embodiment, the toner has a shell layer made of two or more resin layers, and the outermost layer of the shell layer is made of an amorphous resin, which is believed to suppress the deterioration of fine line reproducibility caused by the aggregation of toner particles. For the above reasons, it is presumed that the toner according to this embodiment has high thin line reproducibility.
[0028] The toner according to this embodiment will be described in detail below.
[0029] The toner according to the present embodiment is configured to contain toner particles and, if necessary, an external additive.
[0030] <Toner particles> The toner particles have a core particle having a large particle diameter with a number average particle diameter of 1 μm or more, and a shell layer made of two or more resin layers that covers the surface of the core particle.
[0031] (Core particle) The core particle may have at least a large particle. Examples of the core particle include a core particle consisting of a single large particle (hereinafter also referred to as a "single core particle") and a core particle containing two or more large particles and an amorphous resin (hereinafter also referred to as a "composite core particle").
[0032] -Single core particle- One single core particle is composed of one large particle. When a single core particle is used as the core particle, the function of the large particle is easily exhibited compared to when a composite core particle is used. For example, when a glittering pigment described later is used as the large particle, an image with high glittering is easily obtained by using a single core particle as the core particle. Specifically, when one core particle contains two or more glittering pigments, the glittering of the obtained image may decrease due to the orientation planes of the two or more glittering pigments being different from each other, but the decrease in glittering is easily suppressed by using a single core particle.
[0033] -Composite core particle- The composite core particle is not limited as long as it contains two or more large particles and an amorphous resin. The use of composite core particles as core particles has the advantage of improving the smoothness of the toner fixed image compared to the use of single core particles. Although the reason for this is unclear, it is speculated that the composite core particles have a relatively small size per large particle compared to the size of the toner particles, and the core particles themselves contain an amorphous resin, which makes it difficult for surface irregularities to occur during fixing. The number of large diameter particles contained in the composite core particle is 2 or more, and can be in the range of 2 to 10. From the viewpoint of achieving both low-temperature fixability and bending strength of the image, the number is preferably in the range of 3 to 8, and more preferably in the range of 3 to 6.
[0034] The content of the large diameter particles relative to the entire composite core particle is preferably 50% by mass or more, more preferably 50% by mass or more and 90% by mass or less, and even more preferably 50% by mass or more and 70% by mass or less. By having the content of the large diameter particles in the above range, the function of the large diameter particles is more easily exhibited than when the content is less than the above range. For example, when a glittering pigment described later is used as the large diameter particles, when the content of the large diameter particles is in the above range, an image with high glitteriness is more easily obtained. In addition, by having the content of the large diameter particles in the above range, deterioration of the charging characteristics caused by exposure of the large diameter particles due to loads such as stirring in the developing means is suppressed, and the charging retention is improved, compared to when the content is more than the above range.
[0035] The composite core particle may contain other components in addition to the large particle and the amorphous resin, as necessary. Examples of the other components contained in the composite core particle include a release agent, a crystalline resin, a colorant, and other additives. In addition to the large diameter particle and the amorphous resin, the composite core particle preferably contains at least one selected from the group consisting of a release agent, a crystalline resin, and a colorant, more preferably contains at least one selected from the group consisting of a release agent and a crystalline resin, and even more preferably contains a release agent.
[0036] When composite core particles containing a releasing agent are used as the core particles, the toner can more easily achieve low-temperature fixability compared to a case where no releasing agent is contained. When the composite core particles contain a release agent, the content of the release agent relative to the entire composite core particle is, for example, in the range of 2% by mass or more and 20% by mass or less, and from the viewpoint of low-temperature fixing property and suppression of release agent offset (i.e., suppression of a situation in which part of the release agent remains on the fixing belt due to an excessive amount of release agent), it is preferably in the range of 5% by mass or more and 15% by mass or less.
[0037] Furthermore, when composite core particles containing a crystalline resin are used as the core particles, the toner can more easily achieve low-temperature fixability compared to when no crystalline resin is contained. When the composite core particle contains a crystalline resin, the content of the crystalline resin relative to the entire composite core particle is, for example, in the range of 2% by mass or more and 40% by mass or less, and from the viewpoint of improving low-temperature fixing property and electrostatic chargeability (for example, suppression of charge leakage due to a large amount of crystalline resin, suppression of environmental differences between a high-temperature and high-humidity environment and a low-temperature and low-humidity environment, etc.), it is preferably in the range of 5% by mass or more and 25% by mass or less.
[0038] Furthermore, when composite core particles containing a colorant are used as the core particles, a toner having a color closer to the desired color can be obtained more easily than when no colorant is contained. When the composite core particle contains a colorant, the content of the colorant relative to the entire composite core particle is, for example, in the range of 0.05% by mass to 10% by mass. Each component contained in the core particle will be described below.
[0039] -Large particles- Large particles are particles having a number-average particle size of 1 μm or more. The number average particle size of the large particles is, for example, in the range of 1 μm or more and 10 μm or less. From the viewpoint of color characteristics (e.g., brilliance, phosphorescence, etc.) and fine line reproducibility, the range of 2 μm or more and 9 μm or less is preferable, and the range of 3 μm or more and 8 μm or less is more preferable.
[0040] The number average particle size of the large particles is a value measured using a Coulter Multisizer II (manufactured by Beckman Coulter, Inc.) and an ISOTON-II (manufactured by Beckman Coulter, Inc.) as the electrolyte. For the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 ml of a 5 mass % aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant, and this is then added to 100 ml to 150 ml of the electrolyte. The electrolyte with the sample suspended in it is dispersed for 1 minute using an ultrasonic disperser, and the particle size distribution of particles with diameters in the range of 2 μm to 60 μm is measured using a Coulter Multisizer II with an aperture diameter of 100 μm. The number of particles sampled is 50,000. A cumulative distribution is drawn for each particle size range (channel) divided based on the particle size distribution measured, from the smallest diameter side, and the particle size at which the cumulative 50% occurs is taken as the number-average particle size. The number average particle size of the large particles in the toner may be a value measured by the above method after removing components other than the large particles.
[0041] Specific examples of large-diameter particles include scaly particles such as glittering pigments, and luminescent particles containing luminescent materials. When scaly particles are used as the large particles, toner particles having exposed surfaces of the core particles are more likely to be obtained than when spherical particles are used as the large particles. However, in this embodiment, the coverage of the resin layer on the surfaces of the core particles is increased, so that the deterioration of the fine line reproducibility caused by the exposed surfaces of the core particles is suppressed.
[0042] --Scaly particles-- Examples of the scale-like particles include particles having a ratio of the average length in the major axis direction to the average length in the thickness direction taken as 1 (hereinafter also referred to as the "aspect ratio") of 5 or more, such as luster pigments. Examples of luster pigments, which are one example of scaly particles, include metal powders such as aluminum (metallic Al), brass, bronze, nickel, stainless steel, zinc, etc.; mica coated with titanium oxide, yellow iron oxide, etc.; coated flaky inorganic crystalline substrates such as barium sulfate, layered silicates, layered aluminum silicates, etc.; single crystal plate-like titanium oxide; basic carbonates; bismuth oxychloride; natural guanine; flaky glass powder; and flaky glass powder with metal vapor deposition. Among the bright pigments, metal powders are preferred from the viewpoint of specular reflection intensity, and among these, aluminum is most preferred.
[0043] The average length in the major axis direction of the bright pigment is preferably from 1 μm to 30 μm, more preferably from 3 μm to 20 μm, and even more preferably from 5 μm to 15 μm. The ratio (aspect ratio) of the average length in the major axis direction to the average length in the thickness direction of the shiny pigment is preferably 5 or more and 200 or less, more preferably 10 or more and 100 or less, and even more preferably 30 or more and 70 or less.
[0044] The average length and aspect ratio of each of the brilliant pigments are measured by the following method: Using a scanning electron microscope (S-4800, manufactured by Hitachi High-Technologies Corporation), photographs of pigment particles are taken at a measurable magnification (300 to 100,000 times), and in a state in which the obtained images of the pigment particles are two-dimensionalized, the length in the major axis direction and the length in the thickness direction of each particle are measured, and the average length in the major axis direction and the aspect ratio of the brilliant pigment are calculated.
[0045] --Luminous particles-- The luminescent particles include particles that absorb irradiated light and emit light. The luminescent particles are particles that contain a luminescent material that absorbs irradiated light and emits light, and may be particles made of the luminescent material or particles in which the luminescent material is dispersed in a resin or the like. Examples of the light-emitting material include fluorescent materials that absorb light energy and emit it as fluorescent light, and phosphorescent materials that store absorbed light energy inside and emit it as phosphorescence in a dark place.
[0046] The fluorescent material may be an inorganic fluorescent material or an organic fluorescent material. Examples of inorganic fluorescent materials include those that contain crystals of oxides, sulfides, silicates, phosphates, tungstates, etc. of Ca, Ba, Mg, Zn, Cd, etc. as the main components, with metal elements such as Mn, Zn, Ag, Cu, Sb, Pb, etc., or rare earth elements such as lanthanides added as an activator, and then fired. Examples of organic fluorescent materials include fluorescent brighteners, diaminostilbene, imidazole, coumarin, triazole, carbazole, pyridine, naphthalic acid, and derivatives of imidazolone, fluorescein, mineral oil, thioflavin, eosin, todamine, anthracene, terphenyl, brilliant sulfotravine, basic yellow, eolen, and organic pigment dyes (product names: Lumorgen Color (BASF), FZ6014 (Shin-Roi-Ch)).
[0047] The phosphorescent materials include zinc sulfide (ZnS), zinc silicate (Zn 2 SiO 4 ), zinc cadmium sulfide [(Zn,Cd)S], calcium sulfide (CaS), strontium sulfide (SrS), calcium tungstate (CaWO 4 ), strontium aluminate (SrAl 2 O 4 ), inorganic pigments such as phosphorescent zinc sulfide and zinc hexasulfide, and organic pigments such as Lumogen L Yellow, Lumogen Yellow Orange, and Lumogen L Red Orange. In addition, rare earth elements, particularly Eu and Dy, may be added to the inorganic pigments.
[0048] The fluorescent material and the phosphorescent material may be surface-treated with a surface treatment agent for the purpose of improving dispersibility in the resin. As the surface treatment agent, known surface treatment agents such as various coupling agents or dispersibility improvers are used. Specific examples of the surface treatment agent include silane-based coupling agents, titanate-based coupling agents, aluminate-based coupling agents, zirconate-based coupling agents, etc.
[0049] Examples of resins in which the luminescent material can be dispersed include polyvinyl resins such as polyolefins, polystyrene, acrylic resins, polyacrylonitrile, polyvinyl acetate, polyvinyl alcohol, vinyl chloride, and polyvinyl butyral; vinyl chloride-vinyl acetate copolymers; styrene-acrylic acid copolymers; straight silicone resins composed of organosiloxane bonds and modified versions thereof; fluororesins such as polytetrafluoroethylene, polyvinyl fluoride, and polyvinylidene fluoride; polyesters, polyurethanes, polycarbonates; amino resins; and epoxy resins. These resins may be used alone or in combination. These resins may be crosslinked. Further, examples of the resin in which the light emitting material is dispersed include the amorphous resin used in the toner of this embodiment, which will be described later.
[0050] When the luminescent particles are particles in which a luminescent material is dispersed in a resin, the content of the luminescent material relative to the entire luminescent particle may be, for example, in the range of 5% by mass or more and 40% by mass or less, and may also be in the range of 10% by mass or more and 20% by mass or less. The luminescent particles may be particles in which a fluorescent material is dispersed in a resin, particles in which a phosphorescent material is dispersed in a resin, or particles in which both a fluorescent material and a phosphorescent material are dispersed in a resin.
[0051] -Amorphous resin- Examples of the amorphous resin include vinyl resins made of homopolymers of monomers such as styrenes (e.g., styrene, parachlorostyrene, α-methylstyrene, etc.), (meth)acrylic acid esters (e.g., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (e.g., acrylonitrile, methacrylonitrile, etc.), vinyl ethers (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), and olefins (e.g., ethylene, propylene, butadiene, etc.), or copolymers made of a combination of two or more of these monomers. Examples of the amorphous resin include non-vinyl resins such as epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, and modified rosin, mixtures of these with the vinyl resins, and graft polymers obtained by polymerizing vinyl monomers in the coexistence of these. These amorphous resins may be used alone or in combination of two or more kinds.
[0052] The "crystalline" nature of a resin refers to the presence of a clear endothermic peak rather than a stepwise change in the amount of endothermic heat in differential scanning calorimetry (DSC); specifically, the half-width of the endothermic peak is within 10°C when measured at a heating rate of 10 (°C / min). On the other hand, the term "amorphous" for a resin refers to a half-width exceeding 10° C., a stepwise change in endothermic heat quantity, or no clear endothermic peak being observed.
[0053] As the amorphous resin, a polyester resin is preferable. The amorphous polyester resin may be, for example, a condensation polymer of a polyvalent carboxylic acid and a polyhydric alcohol. The amorphous polyester resin may be a commercially available product or a synthesized product.
[0054] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenylsuccinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). Among these, aromatic dicarboxylic acids are preferable as polyvalent carboxylic acids. The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, anhydrides thereof, and lower (e.g., carbon number 1 to 5) alkyl esters thereof. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.
[0055] Examples of polyhydric alcohols include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, examples of polyhydric alcohols include aromatic diols and alicyclic diols, and more preferably aromatic diols. As the polyhydric alcohol, a polyhydric alcohol having a crosslinked or branched structure of three or more may be used in combination with the diol. Examples of the polyhydric alcohol having a trihydric or higher valence include glycerin, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.
[0056] The glass transition temperature (Tg) of the amorphous polyester resin is preferably 50°C or higher and 80°C or lower, and more preferably 50°C or higher and 65°C or lower. The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, from the "extrapolated glass transition onset temperature" described in the method for determining glass transition temperature in JIS K 7121-1987 "Method for measuring transition temperature of plastics."
[0057] The weight average molecular weight (Mw) of the amorphous polyester resin is preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less. The number average molecular weight (Mn) of the amorphous polyester resin is preferably 2,000 or more and 100,000 or less. The molecular weight distribution Mw / Mn of the amorphous polyester resin is preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less. The weight average molecular weight and number average molecular weight are measured by gel permeation chromatography (GPC). The molecular weight measurement by GPC is performed using a Tosoh GPC HLC-8120GPC as the measuring device, a Tosoh TSKgel SuperHM-M (15 cm) column, and THF solvent. The weight average molecular weight and number average molecular weight are calculated from the measurement results using a molecular weight calibration curve created with a monodisperse polystyrene standard sample.
[0058] The amorphous polyester resin can be obtained by a known manufacturing method, for example, by carrying out the reaction while removing water and alcohol generated during condensation by setting the polymerization temperature to 180° C. or higher and 230° C. or lower, and reducing the pressure in the reaction system as necessary. If the raw material monomer is not soluble or compatible at the reaction temperature, a high boiling point solvent may be added as a solubilizing agent to dissolve it. In this case, the polycondensation reaction is carried out while distilling off the solubilizing agent. If a monomer with poor compatibility is present, it is recommended that the monomer with poor compatibility is condensed in advance with the acid or alcohol to be polycondensed, and then polycondensed with the main component.
[0059] -Release agent- Examples of the release agent include hydrocarbon waxes, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic or mineral / petroleum waxes such as montan wax, and ester waxes such as fatty acid esters and montan acid esters. The release agent is not limited to these.
[0060] The melting temperature of the release agent is preferably 50°C or higher and 110°C or lower, and more preferably 60°C or higher and 100°C or lower. The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "melting peak temperature" described in the method for determining melting temperature in JIS K 7121-1987 "Method for measuring transition temperature of plastics."
[0061] -Crystalline resin- The crystalline resin may be, for example, a crystalline polyester resin. The crystalline polyester resin may be, for example, a polycondensate of a polyvalent carboxylic acid and a polyhydric alcohol. The crystalline polyester resin may be a commercially available product or a synthesized product. Here, the crystalline polyester resin is preferably a polycondensate using a polymerizable monomer having a linear aliphatic group rather than a polymerizable monomer having an aromatic group, since the crystalline polyester resin can easily form a crystalline structure.
[0062] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, and their lower alkyl esters (e.g., carbon number 1 to 5). As the polyvalent carboxylic acid, a dicarboxylic acid having a sulfonic acid group and a dicarboxylic acid having an ethylenic double bond may be used in combination with these dicarboxylic acids. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.
[0063] Examples of polyhydric alcohols include aliphatic diols (for example, straight-chain aliphatic diols having 7 to 20 carbon atoms in the main chain). Examples of aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosanedecanediol. Among these, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol are preferred as aliphatic diols. The polyhydric alcohol may be a trihydric or higher alcohol having a crosslinked or branched structure in combination with the diol. Examples of the trihydric or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.
[0064] Here, the polyhydric alcohol has an aliphatic diol content of 80 mol % or more, preferably 90 mol % or more.
[0065] The melting temperature of the crystalline polyester resin is preferably 50°C or higher and 100°C or lower, more preferably 55°C or higher and 90°C or lower, and even more preferably 60°C or higher and 85°C or lower. The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "melting peak temperature" described in the method for determining melting temperature in JIS K7121-1987 "Method for measuring transition temperature of plastics."
[0066] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably 6,000 or more and 35,000 or less.
[0067] The crystalline polyester resin can be obtained, for example, by a known production method, like the amorphous polyester resin.
[0068] -Coloring agent- Examples of colorants include carbon black, chrome yellow, Hansa Yellow, benzidine yellow, threne yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, Balkan orange, watch young red, permanent red, brilliant carmine 3B, brilliant carmine 6B, DuPont oil red, pyrazolone red, lithol red, rhodamine B lake, lake red C, pigment red, rose bengal, aniline blue, ultramarine blue, and tetrahydrofuran. Examples of the dyes include various pigments such as phosphorus blue, chalcoil blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, and malachite green oxalate, and various dyes such as acridine-based, xanthene-based, azo-based, benzoquinone-based, azine-based, anthraquinone-based, thioindigo-based, dioxazine-based, thiazine-based, azomethine-based, indigo-based, phthalocyanine-based, aniline black-based, polymethine-based, triphenylmethane-based, diphenylmethane-based, and thiazole-based dyes. The colorant may be used alone or in combination of two or more kinds.
[0069] The colorant may be surface-treated as necessary, or may be used in combination with a dispersant. In addition, a plurality of types of colorants may be used in combination.
[0070] -Other additives- Examples of other additives include well-known additives such as magnetic materials, charge control agents, inorganic powders, etc. These additives are contained in the composite core particles as internal additives.
[0071] (Shell layer) The shell layer is composed of two or more resin layers, and includes a resin layer composed of an amorphous resin as the outermost layer of the two or more resin layers. Here, the "outermost layer" is a layer that constitutes the surface of a toner particle, the "innermost layer" is a layer that is in contact with a core particle, and the "middle layer" is a layer other than the outermost layer and the innermost layer. The number of resin layers constituting the shell layer should be at least 2, for example, in the range of 2 to 20. From the viewpoint of fine line reproducibility and ease of production, the number is preferably 3 to 15, and more preferably 3 to 10. When the number of resin layers constituting the shell layer is two, the shell layer is composed of two resin layers arranged in the order of the innermost layer and the outermost layer from the core particle side. When the number of resin layers constituting the shell layer is three, the shell layer is composed of three resin layers arranged in the order of the innermost layer, the intermediate layer, and the outermost layer from the core particle side. When the number of resin layers constituting the shell layer is four, the shell layer is composed of four resin layers arranged in the order of the innermost layer, the first intermediate layer, the second intermediate layer, and the outermost layer from the core particle side.
[0072] Of the two or more resin layers, the outermost layer is a resin layer made of an amorphous resin, while the innermost layer and the intermediate layer contain at least an amorphous resin and may contain a release agent, a crystalline resin, a colorant, other additives, and the like, as necessary. Specific examples of the amorphous resin, release agent, crystalline resin, and colorant contained in the shell layer are the same as the specific examples of the amorphous resin, release agent, crystalline resin, and colorant described as the components contained in the composite core particle. Here, the resin layer made of an amorphous resin is a resin layer to which the release agent, which is a toner constituent material other than the amorphous resin, the crystalline resin, and the release agent are not intentionally added, and may contain components (e.g., aggregating agents, dispersion media, etc.) that are inevitably mixed in during the manufacturing process.
[0073] When the core particle contains a component other than the large particle, the type of each component contained in the shell layer may be the same as or different from the type of each component contained in the core particle. Specifically, for example, when the core particle contains an amorphous polyester resin, the amorphous resin contained in the shell layer may be the same resin as the amorphous polyester resin contained in the core particle, may be a different amorphous polyester resin, or may be an amorphous resin other than polyester resin.
[0074] The resin layers constituting the shell layer may have the same composition or different compositions. It is preferable that adjacent resin layers constituting the shell layer have different compositions. Here, examples of two resin layers having different compositions include two resin layers containing different types of components, two resin layers containing the same types of components but in different ratios, and two resin layers in which some of the components contained in one resin layer are not contained in the other resin layer.
[0075] From the viewpoint of suppressing uneven gloss of the fixed image, the shell layer preferably includes a resin layer containing a release agent. When the number of resin layers constituting the shell layer is two, from the viewpoint of suppressing uneven gloss of the fixed image, the innermost layer preferably contains a release agent. When the number of resin layers constituting the shell layer is three or more, from the viewpoint of suppressing uneven gloss of the fixed image, at least one resin layer selected from the innermost layer and the intermediate layer preferably contains a release agent.
[0076] On the other hand, when the core particles contain a release agent, it is preferable that the innermost layer of the shell layer does not contain a release agent in order to suppress deterioration of the particle size distribution due to aggregation caused by hydrophobic interactions in the production process. In other words, from the viewpoint of achieving both suppression of uneven gloss of the fixed image and suppression of deterioration of the particle size distribution, it is preferable that the shell layer includes three or more resin layers, the innermost layer does not contain a release agent, and the intermediate layer includes a resin layer that contains a release agent.
[0077] From the viewpoint of fine line reproducibility, the shell layer is preferably composed of three or more resin layers, the innermost layer being composed of an amorphous resin, and at least one of the intermediate layers containing an amorphous resin and at least one selected from the group consisting of a release agent, a crystalline resin, and a colorant. By including a resin layer containing at least one selected from the group consisting of a release agent, a crystalline resin, and a colorant as the intermediate layer, electrostatic repulsion is suppressed, and the coverage of the shell layer on the surface of the core particle is likely to be increased.
[0078] From the viewpoint of achieving both improved thermal properties and low-temperature fixability of the toner, the outermost shell layer preferably contains an amorphous resin having a higher glass transition temperature than the amorphous resins contained in the other resin layers. The difference Tg1-Tg2 between the glass transition temperature Tg1 of the amorphous resin contained in the outermost layer of the shell layer and the glass transition temperature Tg2 of the amorphous resin contained in the other resin layers is, for example, in the range of 0°C or more and 15°C or less. From the viewpoint of achieving both improved thermal properties and low-temperature fixability of the toner, the range of 0°C or more and 12°C or less is preferable, and the range of 0°C or more and 10°C or less is more preferable. The Tg1 is, for example, in the range of 45° C. or more and 65° C. or less. From the viewpoint of achieving both improved thermal properties and low-temperature fixability of the toner, the range of 50° C. or more and 63° C. or less is preferable, and the range of 55° C. or more and 61° C. or less is more preferable.
[0079] The mass of the entire shell layer may be, for example, in the range of 100 parts by mass to 450 parts by mass, preferably in the range of 150 parts by mass to 400 parts by mass, and more preferably in the range of 200 parts by mass to 350 parts by mass, relative to 100 parts by mass of the core particle. When the mass of the entire shell layer is in the above range, the coverage rate of the shell layer on the surface of the core particle is higher than when it is less than the above range, and fine line reproducibility is improved. In addition, when the mass of the entire shell layer is in the above range, there is an advantage that the function of the large diameter particle is easily exerted compared to when it is more than the above range. In this embodiment, since the core particle contains a large diameter particle, it is preferable to make the overall mass larger than that of the shell layer that covers the core particle that does not contain a large diameter particle.
[0080] The thickness of the entire shell layer is, for example, in the range of 0.5 μm to 4 μm, preferably in the range of 0.8 μm to 3 μm, and more preferably in the range of 1.2 μm to 2.5 μm. When the thickness of the entire shell layer is in the above range, fine line reproducibility is improved compared to when the thickness is smaller than the above range. In addition, when the thickness of the entire shell layer is in the above range, there is an advantage that the function of the large diameter particles is more easily exerted compared to when the thickness is larger than the above range. The thickness of the entire shell layer is determined by observing the cross section of the toner with a STEM and calculating the distance from the toner surface to the pigment. For example, in a glitter toner using a glitter pigment as a large particle, the thickness of the entire shell layer is measured as follows. Specifically, the glittering toner is embedded in a bisphenol A liquid epoxy resin and a curing agent, and then a cutting sample is prepared. The cutting sample is then cut at -100°C using a cutting machine with a diamond knife (e.g., LEICA Ultramicrotome (manufactured by Hitachi Technologies)) to prepare an observation sample. The cross section of the observation sample is observed at a magnification of about 5000 times using a transmission electron microscope (TEM). For the observed 1000 glittering toner particles, the distance between the toner surface and the large diameter particles in the cross section of the glittering toner particle is calculated using image analysis software.
[0081] (Characteristics of toner particles, etc.) The volume average particle size (D50v) of the toner particles is preferably from 2 μm to 12 μm, and more preferably from 4 μm to 11 μm.
[0082] The various average particle sizes and particle size distribution indexes of the toner particles are measured using a Coulter Multisizer II (manufactured by Beckman Coulter, Inc.), and the electrolyte is measured using an ISOTON-II (manufactured by Beckman Coulter, Inc.). For the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 ml of a 5% aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant, and this is then added to 100 ml to 150 ml of the electrolyte. The electrolyte with the sample suspended in it is dispersed for 1 minute using an ultrasonic disperser, and the particle size distribution of particles with diameters in the range of 2 μm to 60 μm is measured using a Coulter Multisizer II with an aperture diameter of 100 μm. The number of particles sampled is 50,000. Based on the measured particle size distribution, cumulative distributions of volume and number are drawn for each divided particle size range (channel) from the smallest diameter side, and the particle size at 16% of the cumulative size is defined as the volume particle size D16v, the number particle size D16p, the particle size at 50% of the cumulative size as the volume average particle size D50v, the cumulative number average particle size D50p, and the particle size at 84% of the cumulative size as the volume particle size D84v and number particle size D84p. Using these, the volumetric particle size distribution index (GSDv) is (D84v / D16v) 1 / 2 The number size distribution index (GSDp) is (D84p / D16p) 1 / 2 It is calculated as:
[0083] <External additives> The external additive may be, for example, inorganic particles. Examples of the inorganic particles include SiO 2 , TiO 2 , Al 2 O 3 , CuO, ZnO, SnO 2 , CEO 2 , Fe 2 O 3 , MgO, BaO, CaO, K 2 O, Na 2 O, ZrO 2 , CaO SiO 2 , K 2 O (TiO 2 )n, Al 2 O 3 2SiO 2 , CaCO 3 , MgCO 3 , BaSO 4 , MgSO 4 etc.
[0084] The surface of the inorganic particles as an external additive may be subjected to a hydrophobic treatment. The hydrophobic treatment may be performed, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and examples thereof include silane coupling agents, silicone oils, titanate coupling agents, and aluminum coupling agents. These may be used alone or in combination of two or more. The amount of the hydrophobizing agent is usually, for example, 1 part by mass or more and 10 parts by mass or less per 100 parts by mass of the inorganic particles.
[0085] Examples of external additives include resin particles (resin particles such as polystyrene, polymethyl methacrylate (PMMA), and melamine resin), cleaning agents (for example, metal salts of higher fatty acids such as zinc stearate, and fluorine-based polymer particles).
[0086] The amount of the external additive added is, for example, preferably from 0.01% by mass to 5% by mass, and more preferably from 0.01% by mass to 2.0% by mass, based on the toner particles.
[0087] <Resin single particle> The toner of the present embodiment preferably does not contain resin particles alone, or the content of resin particles alone is 80% or less by number of the entire toner. Resin particles alone are particles that contain an amorphous resin and do not contain large-diameter particles. Resin particles alone are formed by agglomeration of amorphous resin particles in the process of coating the surface of a core particle with a resin layer. By making the content of the resin particles alone within the above range, the occurrence of regions in the fixed image where the function of the large-diameter particles is not exerted partially due to the presence of the resin particles alone, which leads to a decrease in granularity, is suppressed, and a fixed image with good granularity is obtained, compared with the case where the content of the resin particles alone is greater than the above range. Also, by making the content of the resin particles alone within the above range, it is easier to obtain toner particles having a high coverage rate of the resin layer on the surface of the core particles, and fine line reproducibility is improved, compared with the case where the content of the resin particles alone is greater than the above range.
[0088] The resin particles alone more preferably account for 50% by number or less of the entire toner, even more preferably 40% by number or less, and particularly preferably are not contained. The content of resin particles alone is measured as follows. Specifically, toner particles are embedded in a bisphenol A type liquid epoxy resin and a curing agent, and then a cutting sample is prepared. The cutting sample is then cut at -100°C using a cutting machine with a diamond knife, such as a LEICA Ultramicrotome (manufactured by Hitachi Technologies), to prepare a sample for observation. The observation sample is observed at a magnification of about 5000 times using a TEM. Large-diameter particles are distinguished from differences in the shading of the observed image due to differences in composition with the binder resin. In this manner, the cross sections of 5,000 toner particles are observed, and the proportion of the number of toner particles that do not contain large diameter particles is calculated.
[0089] <Toner manufacturing method> Next, a method for producing the toner according to the present embodiment will be described. The toner according to the exemplary embodiment is obtained by producing toner particles and then externally adding an external additive to the toner particles.
[0090] Moreover, the toner particles are obtained by coating core particles with a shell layer. Specifically, the toner particles are obtained through a core particle dispersion preparation step of preparing a core particle dispersion in which core particles having large diameter particles with a number average particle size of 1 μm or more are dispersed; a resin particle layer formation step of adding amorphous resin particles to the core particle dispersion and aggregating the amorphous resin particles so as to adhere to the core particles, thereby forming a resin particle layer on the surface of the core particles; a repetition step of repeating the above step one or more times, where the particles added in the final step are only the amorphous resin particles, thereby forming aggregated particles having two or more resin particle layers on the surface of the core particles, the outermost layer of which is made of the amorphous resin particles; and a fusion and coalescence step of heating the aggregated particle dispersion in which the aggregated particles are dispersed, thereby fusing and coalescing the aggregated particles to form toner particles.
[0091] By obtaining toner particles by the above method, a toner that can provide images with excellent thin line reproducibility can be produced, compared to a case in which toner particles are obtained by forming a resin particle layer only once without going through the above repeating process. Specifically, as described above, when the core particles have large diameter particles, it is required to attach a large amount of resin, so that the concentration of amorphous resin particles in the dispersion of the core particles becomes high, and the amorphous resin particles tend to aggregate with each other. As described above, resin particles alone are easily formed, and when a large number of toner particles with the surface of the core particles exposed are formed, the reproducibility of fine lines tends to decrease, and the granularity tends to deteriorate due to the formation of a large number of resin particles alone.
[0092] In contrast, in the above-mentioned manufacturing method, the shell layer is formed through a resin particle layer forming step and a repeating step. In other words, since the shell layer is coated on the surface of the core particle through two or more steps, the concentration of the amorphous resin particles in the dispersion is lower than when the same mass of the resin layer is formed on the surface of the core particle in one step. Therefore, it is considered that the adhesion of the amorphous resin particles to the surface of the core particle is more likely to occur than the aggregation of the amorphous resin particles, and the formation of resin particles alone is suppressed, the coverage rate of the resin layer on the surface of the core particle is increased, and the deterioration of the fine line reproducibility and the deterioration of the graininess are suppressed.
[0093] Furthermore, in the repeated process, since the particles added in the final operation are only amorphous resin particles, the outermost layer of the shell layer is a resin layer made of amorphous resin without containing a release agent, etc., and it is considered that a toner can be obtained in which the deterioration of fine line reproducibility caused by the aggregation of toner particles is suppressed.
[0094] In the resin particle layer forming step and the repeating step, it is preferable that the particles added in the resin particle layer forming step are only amorphous resin particles, and the repeating step is a step of repeating the above operation two or more times, and that the particles added in one or more of the operations in the repeating step except for the last one include amorphous resin particles and at least one type selected from the group consisting of release agent particles, crystalline resin particles, and colorant particles, thereby forming aggregated particles having three or more resin particle layers on the surface of a core particle, an innermost layer of the three or more resin particle layers being made of amorphous resin particles, and an intermediate layer of the three or more resin particle layers being made of amorphous resin particles and at least one type selected from the group consisting of release agent particles, crystalline resin particles, and colorant particles.
[0095] By undergoing the above-mentioned resin particle layer forming process and repeating process, a toner is obtained in which the shell layer is made of three or more resin layers containing an amorphous resin, the innermost layer of the three or more resin layers is made of an amorphous resin, and the intermediate layer of the three or more resin layers is a resin layer containing an amorphous resin and at least one selected from the group consisting of a release agent, a crystalline resin, and a colorant.
[0096] The amorphous resin particles may be added by adding an amorphous resin particle dispersion liquid in which the amorphous resin particles are dispersed. Details of the amorphous resin particle dispersion liquid are the same as those of the amorphous resin particle dispersion liquid used in the production of the composite core particles described later. Each step will be described below.
[0097] (Core particle dispersion preparation process) -Preparation of single core particle dispersion- When the core particles are single core particles, the single core particle dispersion is prepared, for example, by dispersing the single core particles in a dispersion medium with a surfactant. The dispersion medium, surfactant, dispersion method, and content of the core particles used in the preparation of the single core particle dispersion are the same as the dispersion medium, surfactant, dispersion method, and content of the amorphous resin particles used in the preparation of the amorphous resin particle dispersion described later.
[0098] -Preparation of composite core particle dispersion- When the core particles are composite core particles, the composite core particles may be produced by any of a dry production method (e.g., a kneading and grinding method, etc.) and a wet production method (e.g., an aggregation-coalescence method, a suspension polymerization method, a dissolution suspension method, etc.) The production method of the composite core particles is not particularly limited, and a well-known production method is adopted. Among these, it is preferable to obtain composite core particles by the aggregation and coalescence method.
[0099] Specifically, for example, when the composite core particles are produced by the aggregation-coalescence method, The composite core particle dispersion is obtained by manufacturing composite core particles through a step of preparing an amorphous resin particle dispersion in which amorphous resin particles are dispersed (amorphous resin particle dispersion preparation step) and a step of aggregating the amorphous resin particles (or other particles, if necessary) in the amorphous resin particle dispersion (or in a dispersion after mixing other particle dispersions, if necessary) to form composite core aggregated particles (aggregation step).
[0100] The composite core particles may be obtained by, in addition to the amorphous resin particle dispersion preparation step and the aggregation step, a step of heating the composite core aggregate particle dispersion in which the composite core aggregate particles are dispersed to fuse and coalesce the composite core aggregate particles. Details of the above-mentioned step of fusing and coalescing the composite core aggregate particles are the same as the details of the fusion and coalescence step described later. Furthermore, the composite core particle dispersion liquid may be a composite core particle dispersion liquid obtained in the process of producing the composite core particles as is, or a composite core particle dispersion liquid obtained by obtaining composite core particles in a dry state and then dispersing them in a dispersion medium may be used.
[0101] Each step will be described in detail below. In the following description, a method for obtaining composite core particles containing a colorant and a release agent will be described, but the colorant and the release agent are used as necessary. Of course, additives other than the colorant and the release agent, crystalline resins, etc. may also be used.
[0102] --Amorphous resin particle dispersion preparation process-- First, a colorant particle dispersion in which colorant particles are dispersed and a release agent particle dispersion in which release agent particles are dispersed are prepared together with an amorphous resin particle dispersion in which amorphous resin particles are dispersed.
[0103] Here, the amorphous resin particle dispersion liquid is prepared, for example, by dispersing amorphous resin particles in a dispersion medium with the aid of a surfactant.
[0104] The dispersion medium used in the amorphous resin particle dispersion liquid is, for example, an aqueous medium. Examples of the aqueous medium include water such as distilled water and ion-exchanged water, alcohols, etc. These may be used alone or in combination of two or more kinds.
[0105] Examples of the surfactant include anionic surfactants such as sulfate salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. Among these, anionic surfactants and cationic surfactants are particularly preferred. The nonionic surfactants may be used in combination with anionic surfactants or cationic surfactants. The surfactant may be used alone or in combination of two or more kinds.
[0106] In the amorphous resin particle dispersion, examples of a method for dispersing the amorphous resin particles in a dispersion medium include general dispersion methods using, for example, a rotary shear type homogenizer, a ball mill having a medium, a sand mill, a dyno mill, etc. Depending on the type of the amorphous resin particles, the amorphous resin particles may be dispersed in the amorphous resin particle dispersion using, for example, a phase inversion emulsification method. The phase inversion emulsification method is a method in which the resin to be dispersed is dissolved in a hydrophobic organic solvent in which the resin is soluble, a base is added to the organic continuous phase (O phase) to neutralize it, and then an aqueous medium (W phase) is added to effect conversion of the resin from W / O to O / W (so-called phase inversion), resulting in a discontinuous phase, and the resin is dispersed in particulate form in the aqueous medium.
[0107] The volume average particle size of the amorphous resin particles dispersed in the amorphous resin particle dispersion is, for example, preferably from 0.01 μm to 1 μm, more preferably from 0.08 μm to 0.8 μm, and even more preferably from 0.1 μm to 0.6 μm. The volume average particle size of the amorphous resin particles is measured by using a particle size distribution obtained by measurement using a laser diffraction particle size distribution measuring device (e.g., LA-700 manufactured by Horiba, Ltd.), subtracting the cumulative distribution from the small particle size side for the volume of the divided particle size range (channel), and measuring the particle size at which the cumulative distribution is 50% of all particles as the volume average particle size D50v. The volume average particle sizes of particles in other dispersions are also measured in the same manner.
[0108] The content of the amorphous resin particles in the amorphous resin particle dispersion is, for example, preferably from 5% by mass to 50% by mass, and more preferably from 10% by mass to 40% by mass.
[0109] In addition, for example, a colorant particle dispersion and a release agent particle dispersion are also prepared in the same manner as the amorphous resin particle dispersion. That is, the volume average particle size, dispersion medium, dispersion method, and particle content of the particles in the amorphous resin particle dispersion are the same for the colorant particles dispersed in the colorant particle dispersion and the release agent particles dispersed in the release agent particle dispersion.
[0110] --Agglomeration process-- Next, the colorant particle dispersion and the release agent particle dispersion are mixed together with the amorphous resin particle dispersion. Then, in the mixed dispersion, the amorphous resin particles, the colorant particles, and the release agent particles are hetero-aggregated to form composite core aggregate particles containing the amorphous resin particles, the colorant particles, and the release agent particles and having a diameter close to that of the target toner particles.
[0111] Specifically, for example, an aggregating agent is added to the mixed dispersion, the pH of the mixed dispersion is adjusted to be acidic (e.g., pH 2 or more and 5 or less), a dispersion stabilizer is added as necessary, and then the mixed dispersion is heated to a temperature equal to or higher than the glass transition temperature of the amorphous resin particles (specifically, for example, a temperature equal to or higher than the glass transition temperature of the amorphous resin particles -30°C and a temperature equal to or lower than the glass transition temperature -10°C), and the particles dispersed in the mixed dispersion are aggregated to form composite core aggregated particles. In the aggregation, for example, the above-mentioned flocculant may be added to the mixed dispersion at room temperature (e.g., 25°C) while stirring the mixed dispersion with a rotary shear homogenizer, the pH of the mixed dispersion may be adjusted to acidic (e.g., pH 2 or more and 5 or less), and a dispersion stabilizer may be added as necessary, followed by the above-mentioned heating.
[0112] Examples of the flocculant include a surfactant having a polarity opposite to that of the surfactant used as the dispersant added to the mixed dispersion, an inorganic metal salt, and a divalent or higher metal complex. In particular, when a metal complex is used as the flocculant, the amount of surfactant used is reduced and the charging characteristics are improved. If necessary, an additive that forms a complex or a similar bond with the metal ions of the flocculant may be used, and a chelating agent is preferably used as this additive.
[0113] Examples of inorganic metal salts include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate, as well as inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide. The chelating agent may be a water-soluble chelating agent, such as oxycarboxylic acid (e.g., tartaric acid, citric acid, gluconic acid, etc.), iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), ethylenediaminetetraacetic acid (EDTA), etc. The amount of the chelating agent added is, for example, preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, relative to 100 parts by mass of the resin particles. Through the above steps, composite core particles are obtained.
[0114] (Resin particle layer forming process and repeating process) In the resin particle layer forming step, amorphous resin particles are added to a core particle dispersion liquid and agglomerated so that the amorphous resin particles adhere to the core particles, thereby forming a resin particle layer on the surfaces of the core particles. In the repeating step, the operation of adding amorphous resin particles to the core particle dispersion and aggregating the amorphous resin particles so that they adhere to the core particles is repeated one or more times. Then, in the final operation, the particles added to the core particle dispersion are made of only amorphous resin, thereby obtaining aggregated particles. The aggregated particles have two or more resin particle layers at least on the surface of the core particle, and the outermost layer of the two or more resin particle layers is a resin particle layer made of amorphous resin particles.
[0115] The addition of the amorphous resin particles in each operation of the resin particle layer forming step and the repeating step is carried out, for example, by adding an amorphous resin particle dispersion liquid in which the amorphous resin particles are dispersed. The details of the amorphous resin particle dispersion liquid are the same as those of the amorphous resin particle dispersion liquid used in the production of the composite core particles described above.
[0116] When the above operation is an operation for forming a resin particle layer made of amorphous resin particles, that is, when a resin layer made of an amorphous resin is formed among the resin layers in the shell layer of the toner particles, for example, the dispersion liquid to be added is made to be only an amorphous resin particle dispersion liquid. Furthermore, when the above-mentioned operation is an operation for forming a resin particle layer containing release agent particles, that is, when a resin layer containing a release agent is formed among the resin layers in the shell layer of the toner particles, for example, a release agent particle dispersion is added in addition to the amorphous resin particle dispersion. Similarly, when the above operation is an operation for forming a resin particle layer containing crystalline resin particles, that is, when forming a resin layer containing a crystalline resin among the resin layers in the shell layer of the toner particles, for example, a crystalline resin particle dispersion is added in addition to an amorphous resin particle dispersion. Furthermore, when the above operation is an operation for forming a resin particle layer containing colorant particles, that is, when forming a resin layer containing a colorant among the resin layers in the shell layer of the toner particles, for example, a colorant particle dispersion is added in addition to the amorphous resin particle dispersion. The details of the release agent particle dispersion, the crystalline resin particle dispersion, and the colorant particle dispersion used in the above-mentioned operations are the same as the details of the release agent particle dispersion, the crystalline resin particle dispersion, and the colorant particle dispersion used in the production of the composite core particles described above.
[0117] The amount of amorphous resin particles added in each operation of the repeating process is preferably greater than the amount of amorphous resin particles added in the previous operation. Since the area of the resin particle layer to be covered increases toward the outside, the amount of amorphous resin particles required to form a resin particle layer of the same thickness is also thought to increase. Therefore, by increasing the amount of amorphous resin particles added, aggregated particles with a high coverage rate by the resin particle layer are obtained, and a toner with high fine line reproducibility is obtained. The rate of increase in the amount of amorphous resin particles added is not particularly limited. For example, when the amount of amorphous resin particles added when forming the innermost layer is A parts by mass and the amount of amorphous resin particles added when forming the outermost layer is B parts by mass, the ratio B / A is preferably greater than 1, more preferably 1.2 or more and 10 or less, and even more preferably 1.5 or more and 8 or less.
[0118] In the above-mentioned operation, amorphous resin particles are added to a core particle dispersion liquid, and then the core particles and the amorphous resin particles are hetero-aggregated in the core particle dispersion liquid to which the amorphous resin particle dispersion liquid has been added, thereby forming a resin particle layer on the surface of the core particles. Specifically, for example, an aggregating agent is added to the core particle dispersion to which the amorphous resin particle dispersion has been added, the pH of the dispersion is adjusted to be acidic (e.g., a pH of 2 or more and 5 or less), a dispersion stabilizer is added as necessary, and then the mixture is heated to a temperature (hereinafter also referred to as the "aggregation temperature") that is the glass transition temperature of the amorphous resin particles (specifically, for example, a temperature that is the glass transition temperature of the amorphous resin particles minus 30°C or more and the glass transition temperature minus 10°C or less) to aggregate the particles dispersed in the dispersion, thereby forming a resin particle layer on the surface of the core particles. In the resin particle layer formation process, for example, the core particle dispersion to which the amorphous resin particle dispersion has been added may be stirred with a rotary shear homogenizer while the above-mentioned coagulant is added at room temperature (e.g., 25°C), the pH of the mixed dispersion may be adjusted to an acidic state (e.g., pH 2 or more and 5 or less), and a dispersion stabilizer may be added as necessary, followed by the above-mentioned heating.
[0119] Details of the flocculant used in the resin particle layer forming step and the additives that may be used as necessary are the same as those of the flocculant and additives used in the aggregating step in the production of the composite core particles described above.
[0120] In all operations of the resin particle layer forming step and the repeating step, it is preferable to add a flocculant to the core particle dispersion in addition to the amorphous resin particles. For example, in the repeating step, when the core particle dispersion to which the amorphous resin particle dispersion has been added already contains a flocculant, the resin particle layer may be formed without adding a flocculant. On the other hand, by adding a flocculant in all operations of the resin particle layer forming step and the repeating step, an appropriate flocculant concentration is maintained throughout all operations, and the coverage rate by the resin particle layer is likely to be high.
[0121] The aggregation temperature in each operation of the repeating step is preferably higher than the aggregation temperature in the immediately preceding operation. Since the resin particle layer tends to become unstable toward the outside, by increasing the aggregation temperature, stable aggregated particles in the resin particle layer can be easily obtained. The degree of increase in the aggregation temperature is not particularly limited. For example, when the aggregation temperature when the innermost layer is formed is E°C and the aggregation temperature when the outermost layer is formed is F°C, the difference (F°C-E°C) is preferably 2°C or more, more preferably 4°C or more and 15°C or less, and even more preferably 6°C or more and 12°C or less.
[0122] (fusion / unification process) Next, the aggregated particle dispersion liquid in which the aggregated particles are dispersed is heated, for example, to a temperature equal to or higher than the glass transition temperature of the amorphous resin particles (for example, a temperature 10 to 30° C. higher than the glass transition temperature of the amorphous resin particles) to fuse and coalesce the aggregated particles, thereby forming toner particles.
[0123] Through the above steps, toner particles are obtained.
[0124] After the fusion and coalescence process, the toner particles formed in the solution are subjected to a known washing process, solid-liquid separation process, and drying process to obtain toner particles in a dried state. In the washing step, it is preferable to carry out sufficient replacement washing with ion-exchanged water from the viewpoint of electrostatic charge. In addition, the solid-liquid separation step is not particularly limited, but it is preferable to carry out suction filtration, pressure filtration, etc. from the viewpoint of productivity. In addition, in the drying step, there is no particular limit to the method, but it is preferable to carry out freeze drying, air flow drying, fluidized drying, vibration type fluidized drying, etc. from the viewpoint of productivity.
[0125] The toner according to the present embodiment is produced, for example, by adding an external additive to the obtained toner particles in a dry state and mixing them. The mixing may be performed, for example, by using a V blender, a Henschel mixer, a Loedige mixer, etc. Furthermore, if necessary, coarse particles of the toner may be removed using a vibration sieve, an air sieve, etc.
[0126] [Electrostatic image developer] The electrostatic image developer according to this embodiment contains at least the toner according to this embodiment. The electrostatic image developer according to the present embodiment may be a one-component developer containing only the toner according to the present embodiment, or may be a two-component developer in which the toner is mixed with a carrier.
[0127] The carrier is not particularly limited, and may be any known carrier, such as a coated carrier in which the surface of a core material made of magnetic powder is coated with a coating resin, a magnetic powder dispersion type carrier in which magnetic powder is dispersed and mixed in a matrix resin, or a resin impregnated type carrier in which porous magnetic powder is impregnated with a resin. The magnetic powder dispersion type carrier and the resin impregnated type carrier may be a carrier in which the constituent particles of the carrier are used as a core material and are coated with a coating resin.
[0128] Examples of the magnetic powder include magnetic metals such as iron, nickel, and cobalt, and magnetic oxides such as ferrite and magnetite.
[0129] Examples of the coating resin and matrix resin include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylic acid ester copolymer, straight silicone resin containing an organosiloxane bond or a modified product thereof, fluororesin, polyester, polycarbonate, phenolic resin, and epoxy resin. The coating resin and the matrix resin may contain other additives such as conductive particles. Examples of the conductive particles include particles of metals such as gold, silver, and copper, carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, and potassium titanate.
[0130] Here, in order to coat the surface of the core material with a coating resin, a method of coating with a coating layer forming solution in which the coating resin and, if necessary, various additives are dissolved in an appropriate solvent can be mentioned. The solvent is not particularly limited and may be selected taking into consideration the coating resin to be used, the suitability for application, etc. Specific resin coating methods include an immersion method in which the core material is immersed in a solution for forming a coating layer, a spray method in which the solution for forming a coating layer is sprayed onto the surface of the core material, a fluidized bed method in which the solution for forming a coating layer is sprayed onto the core material while it is suspended in flowing air, and a kneader coater method in which the core material of a carrier and the solution for forming a coating layer are mixed in a kneader coater and the solvent is removed.
[0131] In the two-component developer, the mixture ratio (mass ratio) of the toner and the carrier is preferably toner:carrier=1:100 to 30:100, and more preferably 3:100 to 20:100.
[0132] [Image forming device / image forming method] An image forming apparatus / image forming method according to this embodiment will be described. The image forming apparatus according to the present embodiment includes an image carrier, a charging means for charging the surface of the image carrier, an electrostatic image forming means for forming an electrostatic image on the surface of the charged image carrier, a developing means for containing an electrostatic image developer and developing the electrostatic image formed on the surface of the image carrier as a toner image with the electrostatic image developer, a transfer means for transferring the toner image formed on the surface of the image carrier to the surface of a recording medium, and a fixing means for fixing the toner image transferred to the surface of the recording medium. The electrostatic image developer according to the present embodiment is used as the electrostatic image developer.
[0133] In the image forming apparatus according to this embodiment, an image forming method (the image forming method according to this embodiment) is carried out, which includes a charging step of charging the surface of an image carrier, an electrostatic image forming step of forming an electrostatic image on the surface of the charged image carrier, a developing step of developing the electrostatic image formed on the surface of the image carrier as a toner image using the electrostatic image developer according to this embodiment, a transfer step of transferring the toner image formed on the surface of the image carrier to the surface of a recording medium, and a fixing step of fixing the toner image transferred to the surface of the recording medium.
[0134] The image forming apparatus according to the present embodiment may be any of known image forming apparatuses, such as a direct transfer type apparatus in which a toner image formed on the surface of an image holder is directly transferred to a recording medium; an intermediate transfer type apparatus in which a toner image formed on the surface of an image holder is primarily transferred to the surface of an intermediate transfer body, and the toner image transferred to the surface of the intermediate transfer body is then secondarily transferred to the surface of a recording medium; an apparatus equipped with a cleaning means for cleaning the surface of the image holder before charging after the transfer of the toner image; and an apparatus equipped with a discharging means for irradiating the surface of the image holder with discharging light to discharge it before charging after the transfer of the toner image. In the case of an intermediate transfer type device, the transfer means has, for example, an intermediate transfer body onto whose surface a toner image is transferred, a primary transfer means which primarily transfers the toner image formed on the surface of the image carrier onto the surface of the intermediate transfer body, and a secondary transfer means which secondarily transfers the toner image transferred onto the surface of the intermediate transfer body onto the surface of a recording medium.
[0135] In the image forming apparatus according to the present embodiment, for example, a portion including the developing means may have a cartridge structure (process cartridge) that is detachably attached to the image forming apparatus. As the process cartridge, for example, a process cartridge including a developing means that contains the electrostatic image developer according to the present embodiment is preferably used.
[0136] An example of an image forming apparatus according to the present embodiment will be described below, but the present invention is not limited to this. Note that only the main parts shown in the drawings will be described, and descriptions of the rest will be omitted.
[0137] FIG. 1 is a schematic diagram showing the configuration of an image forming apparatus according to the present embodiment. The image forming apparatus shown in Fig. 1 includes first to fourth electrophotographic image forming units 10Y, 10M, 10C, and 10K (image forming means) that output images of each color of yellow (Y), magenta (M), cyan (C), and black (K) based on color-separated image data. These image forming units (hereinafter sometimes simply referred to as "units") 10Y, 10M, 10C, and 10K are arranged in parallel at predetermined distances from each other in the horizontal direction. These units 10Y, 10M, 10C, and 10K may be process cartridges that are detachable from the image forming apparatus.
[0138] Above each of the units 10Y, 10M, 10C, and 10K in the drawing, an intermediate transfer belt 20 is provided as an intermediate transfer body extending through each unit. The intermediate transfer belt 20 is provided wound around a drive roll 22 and a support roll 24 that are arranged from left to right in the drawing at a distance from each other and contact the inner surface of the intermediate transfer belt 20, and is adapted to run in a direction from the first unit 10Y to the fourth unit 10K. Note that a force is applied to the support roll 24 in a direction away from the drive roll 22 by a spring or the like (not shown), and tension is applied to the intermediate transfer belt 20 wound around them. In addition, an intermediate transfer body cleaning device 30 is provided on the image carrier side of the intermediate transfer belt 20, facing the drive roll 22. Further, the developing devices (developing means) 4Y, 4M, 4C, and 4K of the units 10Y, 10M, 10C, and 10K are supplied with toner including four colors of toner, yellow, magenta, cyan, and black, contained in toner cartridges 8Y, 8M, 8C, and 8K, respectively.
[0139] Since the first to fourth units 10Y, 10M, 10C, and 10K have the same configuration, the first unit 10Y that forms a yellow image and is disposed upstream in the direction in which the intermediate transfer belt travels will be described here as a representative example. Note that by assigning reference numerals of magenta (M), cyan (C), and black (K) instead of yellow (Y) to parts equivalent to those of the first unit 10Y, descriptions of the second to fourth units 10M, 10C, and 10K will be omitted.
[0140] The first unit 10Y has a photoconductor 1Y that acts as an image carrier. Around the photoconductor 1Y, a charging roll (an example of a charging means) 2Y that charges the surface of the photoconductor 1Y to a predetermined potential, an exposure device (an example of an electrostatic image forming means) 3 that exposes the charged surface to a laser beam 3Y based on a color-separated image signal to form an electrostatic image, a developing device (an example of a developing means) 4Y that supplies charged toner to the electrostatic image to develop it, a primary transfer roll 5Y (an example of a primary transfer means) that transfers the developed toner image onto an intermediate transfer belt 20, and a photoconductor cleaning device (an example of a cleaning means) 6Y that removes toner remaining on the surface of the photoconductor 1Y after the primary transfer are arranged in this order. The primary transfer roll 5Y is disposed inside the intermediate transfer belt 20 and is provided at a position facing the photoconductor 1Y. Furthermore, a bias power supply (not shown) that applies a primary transfer bias is connected to each of the primary transfer rolls 5Y, 5M, 5C, and 5K. Each bias power supply varies the transfer bias applied to each primary transfer roll under the control of a control unit (not shown).
[0141] Hereinafter, an operation of forming a yellow image in first unit 10Y will be described. First, prior to operation, the surface of the photoconductor 1Y is charged to a potential of −600V to −800V by the charging roll 2Y. The photoconductor 1Y has a conductivity (for example, a volume resistivity at 20° C. of 1×10 -6The photosensitive layer is formed by laminating a photosensitive layer on a substrate having a resistivity of Ωcm or less. This photosensitive layer is usually highly resistive (the resistance of ordinary resins), but when irradiated with a laser beam 3Y, the resistivity of the portion irradiated with the laser beam changes. A laser beam 3Y is output to the charged surface of the photoreceptor 1Y via an exposure device 3 in accordance with image data for yellow sent from a control unit (not shown). The laser beam 3Y is irradiated onto the photosensitive layer on the surface of the photoreceptor 1Y, and an electrostatic charge image of a yellow image pattern is formed on the surface of the photoreceptor 1Y.
[0142] An electrostatic image is an image formed on the surface of the photoconductor 1Y by electrostatic charging. The laser beam 3Y reduces the resistivity of the irradiated parts of the photosensitive layer, causing the charged charges on the surface of the photoconductor 1Y to flow, while the charges remain in the parts not irradiated by the laser beam 3Y. This is a so-called negative latent image. The electrostatic image formed on the photoconductor 1Y is rotated to a predetermined developing position as the photoconductor 1Y travels. Then, at this developing position, the electrostatic image on the photoconductor 1Y is made visible as a toner image (developed image) by the developing device 4Y.
[0143] The developing device 4Y contains an electrostatic image developer including at least yellow toner and a carrier, for example. The yellow toner is triboelectrically charged by being stirred inside the developing device 4Y, and is held on a developer roll (an example of a developer holder) with a charge of the same polarity (negative polarity) as the charge on the photoconductor 1Y. As the surface of the photoconductor 1Y passes through the developing device 4Y, the yellow toner electrostatically adheres to the discharged latent image portion on the surface of the photoconductor 1Y, and the latent image is developed with the yellow toner. The photoconductor 1Y on which the yellow toner image has been formed continues to travel at a predetermined speed, and the toner image developed on the photoconductor 1Y is transported to a predetermined primary transfer position.
[0144] When the yellow toner image on the photoreceptor 1Y is transported to the primary transfer, a primary transfer bias is applied to the primary transfer roll 5Y, and an electrostatic force from the photoreceptor 1Y toward the primary transfer roll 5Y acts on the toner image, and the toner image on the photoreceptor 1Y is transferred onto the intermediate transfer belt 20. The transfer bias applied at this time has a polarity (+) opposite to the polarity (-) of the toner, and in the first unit 10Y, for example, it is controlled to +10 μA by a control unit (not shown). On the other hand, the toner remaining on the photoconductor 1Y is removed and collected by the photoconductor cleaning device 6Y.
[0145] Further, the primary transfer bias applied to the primary transfer rolls 5M, 5C, and 5K subsequent to the second unit 10M is also controlled in accordance with the first unit. In this manner, the intermediate transfer belt 20 onto which the yellow toner image has been transferred by the first unit 10Y is conveyed successively through the second to fourth units 10M, 10C, and 10K, where the toner images of the respective colors are transferred in a superimposed manner.
[0146] The intermediate transfer belt 20 onto which the four color toner images have been transferred in multiple layers through the first to fourth units reaches a secondary transfer section that is composed of the intermediate transfer belt 20, a support roll 24 that contacts the inner surface of the intermediate transfer belt, and a secondary transfer roll (an example of a secondary transfer means) 26 arranged on the image bearing surface side of the intermediate transfer belt 20. Meanwhile, a recording paper (an example of a recording medium) P is fed at a predetermined timing into the gap between the secondary transfer roll 26 and the intermediate transfer belt 20 via a supply mechanism, and a secondary transfer bias is applied to the support roll 24. The transfer bias applied at this time has a (-) polarity that is the same as the (-) polarity of the toner, and an electrostatic force from the intermediate transfer belt 20 toward the recording paper P acts on the toner image, so that the toner image on the intermediate transfer belt 20 is transferred onto the recording paper P. The secondary transfer bias at this time is determined according to the resistance detected by a resistance detection means (not shown) that detects the resistance of the secondary transfer section, and is voltage-controlled.
[0147] Thereafter, the recording paper P is sent to a pressure contact portion (nip portion) of a pair of fixing rolls in a fixing device (one example of a fixing means) 28, where the toner image is fixed onto the recording paper P, forming a fixed image.
[0148] The recording paper P onto which the toner image is transferred can be, for example, plain paper used in electrophotographic copying machines, printers, etc. In addition to the recording paper P, other examples of the recording medium include overhead projector sheets, etc. To further improve the smoothness of the image surface after fixing, it is preferable that the surface of the recording paper P is also smooth. For example, coated paper in which the surface of ordinary paper is coated with resin or the like, art paper for printing, etc. are preferably used.
[0149] After the color image has been fixed, the recording paper P is conveyed toward the discharge section, and the series of color image forming operations is completed.
[0150] [Process cartridge / toner cartridge] The process cartridge according to this embodiment will be described. The process cartridge according to this embodiment is a process cartridge that contains the electrostatic image developer according to this embodiment, is equipped with a developing means that develops an electrostatic image formed on the surface of an image carrier using the electrostatic image developer into a toner image, and is detachably attached to an image forming apparatus.
[0151] In addition, the process cartridge according to this embodiment is not limited to the above configuration, and may be configured to include a developing device and, as necessary, at least one other means selected from an image carrier, a charging means, an electrostatic image forming means, and a transfer means.
[0152] An example of a process cartridge according to the present embodiment will be described below, but the present invention is not limited to this example. Note that only the main parts shown in the drawings will be described, and descriptions of the rest will be omitted.
[0153] FIG. 2 is a schematic diagram showing the process cartridge according to the present embodiment. The process cartridge 200 shown in FIG. 2 is configured by, for example, a housing 117 having a mounting rail 116 and an opening 118 for exposure, and integrally combining and holding a photoconductor 107 (an example of an image carrier), a charging roll 108 (an example of a charging means) provided around the photoconductor 107, a developing device 111 (an example of a developing means), and a photoconductor cleaning device 113 (an example of a cleaning means), which are assembled into a cartridge. In FIG. 2, 109 denotes an exposure device (an example of an electrostatic image forming means), 112 denotes a transfer device (an example of a transfer means), 115 denotes a fixing device (an example of a fixing means), and 300 denotes recording paper (an example of a recording medium).
[0154] Next, the toner cartridge according to this embodiment will be described. The toner cartridge according to the present embodiment is a toner cartridge that contains the toner according to the present embodiment and is detachably attached to an image forming apparatus. The toner cartridge contains replenishment toner to be supplied to a developing unit provided in the image forming apparatus.
[0155] 1 is an image forming apparatus having a configuration in which toner cartridges 8Y, 8M, 8C, and 8K can be attached and detached, and the developing devices 4Y, 4M, 4C, and 4K are connected to the toner cartridges corresponding to the respective developing devices (colors) through toner supply pipes (not shown). When the toner contained in the toner cartridge becomes low, the toner cartridge is replaced. EXAMPLES
[0156] Examples will be described below, but the present invention is not limited to these examples. In the following description, unless otherwise specified, all "parts" and "%" are based on mass.
[0157] [Preparation of each particle dispersion] <Preparation of glitter pigment dispersion> Luminescent pigment (aluminum pigment paste, Toyo Aluminum's 2173EA, number-average particle size 6.3 μm, average length in the long axis direction 5.8 μm, aspect ratio 52): 100 parts Anionic surfactant (Daiichi Kogyo Seiyaku's Neogen R): 1.5 parts Ion-exchanged water: 900 parts After removing the solvent from the aluminum pigment paste, the above materials were mixed and dispersed for 1 hour using an emulsifying disperser (Pacific Machinery's Cavitron CR1010) to obtain a glittering pigment dispersion (solids concentration 10% by mass).
[0158] <Preparation of luminescent particle dispersion> Luminous particles (luminous pigment, Nemoto Specialty Chemicals, product number LumiNova Effect Green N-FF, volume average particle size 3.2 μm, number average particle size 2.9 μm): 100 parts Anionic surfactant (Daiichi Kogyo Seiyaku's Neogen R): 1.5 parts Ion-exchanged water: 900 parts The above materials were mixed and dispersed for 1 hour using an emulsifying disperser (Cavitron CR1010 manufactured by Pacific Machinery Co., Ltd.) to obtain a luminescent particle dispersion (solid concentration: 10% by mass).
[0159] <Preparation of amorphous polyester resin particle dispersion (1)> In a reaction vessel equipped with a stirrer, a thermometer, a condenser, and a nitrogen gas inlet tube, 80 mol parts of polyoxypropylene (2,2)-2,2-bis (4-hydroxyphenyl) propane, 10 mol parts of ethylene glycol, 10 mol parts of cyclohexanediol, 80 mol parts of terephthalic acid, 10 mol parts of isophthalic acid, and 10 mol parts of n-dodecenyl succinic acid were charged, and the atmosphere in the reaction vessel was replaced with dry nitrogen gas. Then, 0.25 mass parts of titanium tetrabutoxide was charged as a catalyst with respect to 100 mass parts of the monomer component. After stirring and reacting for 3 hours at 170°C under a nitrogen gas flow, the temperature was further raised to 210°C over 1 hour, the pressure in the reaction vessel was reduced to 3 kPa, and the reaction was stirred and reacted under reduced pressure for 13 hours to obtain an amorphous polyester resin (1) having a weight average molecular weight of 5,320 and a glass transition temperature of 60.1°C.
[0160] Next, 200 parts by mass of amorphous polyester resin (1), 100 parts by mass of methyl ethyl ketone, and 70 parts by mass of isopropyl alcohol were placed in a jacketed 3-liter reaction tank (Tokyo Rikakikai Co., Ltd.: BJ-30N) equipped with a condenser, a thermometer, a water dropping device, and an anchor blade, and the resin was dissolved by stirring and mixing at 100 rpm while maintaining the temperature at 70 ° C. in a water circulation type thermostatic bath. After that, the stirring speed was set to 150 rpm, the water circulation type thermostatic bath was set to 66 ° C., and 10 parts by mass of 10% by mass ammonia water (reagent) was added over 10 minutes, and then 600 parts by mass of ion-exchanged water kept at 66 ° C. was dropped at a rate of 5 parts by mass / min to invert the phase, and an emulsion was obtained. 600 parts of the obtained emulsion and 525 parts by mass of ion-exchanged water were placed in a 2-liter eggplant flask and set in an evaporator (manufactured by Tokyo Rikakikai Co., Ltd.) equipped with a vacuum control unit via a trap bulb. The eggplant flask was rotated and heated in a hot water bath at 60°C, and the pressure was reduced to 7 kPa while taking care not to bump, to remove the solvent. When the amount of recovered solvent reached 825 parts by mass, the pressure was returned to normal, and the eggplant flask was water-cooled to obtain a dispersion in which resin particles with a volume average particle size of 160 nm were dispersed. Ion-exchanged water was added to obtain an amorphous polyester resin particle dispersion (1) with a solid content concentration of 20% by mass.
[0161] <Preparation of amorphous polyester resin particle dispersion (2)> In a reaction vessel equipped with a stirrer, a thermometer, a condenser, and a nitrogen gas inlet tube, 30 mol parts of polyoxypropylene (2,2)-2,2-bis (4-hydroxyphenyl) propane, 70 mol parts of ethylene glycol, 20 mol parts of cyclohexanediol, 80 mol parts of terephthalic acid, 20 mol parts of isophthalic acid, and 20 mol parts of n-dodecenyl succinic acid were charged, and the atmosphere in the reaction vessel was replaced with dry nitrogen gas. Then, 0.25 mass parts of titanium tetrabutoxide was charged as a catalyst with respect to 100 mass parts of the monomer component. After stirring and reacting for 3 hours at 170°C under a nitrogen gas flow, the temperature was further raised to 210°C over 1 hour, the pressure in the reaction vessel was reduced to 3 kPa, and the reaction was stirred and reacted under reduced pressure for 13 hours to obtain an amorphous polyester resin (2) having a weight average molecular weight of 8,130 and a glass transition temperature of 56.1°C.
[0162] Next, 200 parts by mass of amorphous polyester resin (2), 100 parts by mass of methyl ethyl ketone, and 70 parts by mass of isopropyl alcohol were placed in a jacketed 3-liter reaction tank (Tokyo Rikakikai Co., Ltd.: BJ-30N) equipped with a condenser, a thermometer, a water dropping device, and an anchor blade, and the resin was dissolved by stirring and mixing at 100 rpm while maintaining the temperature at 70 ° C. in a water circulation type thermostatic bath. After that, the stirring speed was set to 150 rpm, the water circulation type thermostatic bath was set to 66 ° C., and 10 parts by mass of 10% by mass ammonia water (reagent) was added over 10 minutes, and then 600 parts by mass of ion-exchanged water kept at 66 ° C. was dropped at a rate of 5 parts by mass / min to invert the phase, and an emulsion was obtained. 600 parts of the obtained emulsion and 525 parts by mass of ion-exchanged water were placed in a 2-liter eggplant flask and set in an evaporator (manufactured by Tokyo Rikakikai Co., Ltd.) equipped with a vacuum control unit via a trap bulb. The eggplant flask was rotated and heated in a hot water bath at 60°C, and the pressure was reduced to 7 kPa while taking care not to bump, to remove the solvent. When the amount of recovered solvent reached 825 parts by mass, the pressure was returned to normal pressure, and the eggplant flask was water-cooled to obtain a dispersion in which resin particles with a volume average particle size of 165 nm were dispersed. Ion-exchanged water was added to obtain an amorphous polyester resin particle dispersion (2) with a solid content concentration of 20% by mass.
[0163] <Preparation of amorphous polyester resin particle dispersion (3)> Bisphenol A ethylene oxide 2 mole adduct: 20 mole% Bisphenol A propylene oxide 2 mole adduct: 30 mole% Terephthalic acid: 30 mol% Dodecenylsuccinic anhydride: 10 mol% Trimellitic anhydride: 10 mol% The above monomer components were charged into a reaction vessel equipped with a stirrer, a thermometer, a condenser, and a nitrogen gas inlet tube, and the inside of the reaction vessel was replaced with dry nitrogen gas. Then, 1.0% of dibutyltin oxide based on the total amount of the above monomer components was added as a catalyst, and the mixture was reacted with stirring at about 190°C for 6 hours under a nitrogen gas stream. The temperature was then increased to 240°C and the mixture was reacted with stirring for 6 hours. After that, the pressure inside the reaction vessel was reduced to 10.0 mmHg, and the mixture was reacted with stirring under reduced pressure for 0.5 hours to obtain an amorphous polyester resin (3) having a weight average molecular weight of 9,430 and a glass transition temperature of 65°C.
[0164] Next, 200 parts by mass of amorphous polyester resin (3), 100 parts by mass of methyl ethyl ketone, and 70 parts by mass of isopropyl alcohol were placed in a jacketed 3-liter reaction tank (Tokyo Rikakikai Co., Ltd.: BJ-30N) equipped with a condenser, a thermometer, a water dropping device, and an anchor blade, and the resin was dissolved by stirring and mixing at 100 rpm while maintaining the temperature at 70 ° C. in a water circulation type thermostatic bath. After that, the stirring speed was set to 150 rpm, the water circulation type thermostatic bath was set to 66 ° C., and 10 parts by mass of 10% by mass ammonia water (reagent) was added over 10 minutes, and then 600 parts by mass of ion-exchanged water kept at 66 ° C. was dropped at a rate of 5 parts by mass / min to invert the phase, and an emulsion was obtained. 600 parts of the obtained emulsion and 525 parts by mass of ion-exchanged water were placed in a 2-liter eggplant flask and set in an evaporator (manufactured by Tokyo Rikakikai Co., Ltd.) equipped with a vacuum control unit via a trap bulb. The eggplant flask was rotated and heated in a hot water bath at 60°C, and the pressure was reduced to 7 kPa while taking care not to bump, to remove the solvent. When the amount of recovered solvent reached 825 parts by mass, the pressure was returned to normal pressure, and the eggplant flask was water-cooled to obtain a dispersion in which resin particles with a volume average particle size of 163 nm were dispersed. Ion-exchanged water was added to obtain an amorphous polyester resin particle dispersion (3) with a solid content concentration of 20% by mass.
[0165] <Preparation of Crystalline Polyester Resin Particle Dispersion> 1,10-Decanedicarboxylic acid: 260 parts by weight 1,6-Hexanediol: 167 parts by weight Dibutyltin oxide (catalyst): 0.3 parts by weight The above materials were placed in a heated and dried three-necked flask, the air in the flask was replaced with nitrogen gas to create an inert atmosphere, and the mixture was stirred and refluxed at 180°C for 5 hours using mechanical stirring. The temperature was then gradually increased to 230°C under reduced pressure and stirred for 2 hours, and when the mixture became viscous, it was air-cooled to stop the reaction. Thus, a crystalline polyester resin with a weight average molecular weight of 12600 and a melting temperature of 73°C was obtained.
[0166] 90 parts of crystalline polyester resin, 1.8 parts of anionic surfactant (TaycaPower, manufactured by Tayca Corporation) and 210 parts of ion-exchanged water were mixed, heated to 120°C, dispersed using a homogenizer (Ultra Turrax T50 manufactured by IKA Corporation), and then dispersed for 1 hour using a pressure discharge type Gaulin homogenizer to obtain a resin particle dispersion in which resin particles having a volume average particle size of 160 nm were dispersed. Ion-exchanged water was added to this resin particle dispersion to adjust the solid content to 20 mass%, and a crystalline polyester resin particle dispersion was obtained.
[0167] <Preparation of release agent particle dispersion> Paraffin wax (manufactured by Nippon Seiro Co., Ltd., FNP92, endothermic peak onset 81°C): 45 parts by mass Anionic surfactant (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Neogen RK): 5 parts by weight Ion-exchanged water: 200 parts by weight The above was mixed and heated to 95°C, and dispersed using a homogenizer (IKA Ultra Turrax T50). After that, dispersion processing was performed using a Manton-Gaulin high pressure homogenizer (Gaulin), and a release agent particle dispersion liquid (solid content concentration: 20% by mass) in which the release agent particles were dispersed was prepared. The volume average particle size of the release agent particles was 0.19 μm.
[0168] <Preparation of Colorant Particle Dispersion> Yellow pigment (BASF, HANSA BRILLIANT YELLOW 5GX 03 (Pigment Yellow 74)): 98 parts by weight Anionic surfactant (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Neogen R): 2 parts by weight Ion-exchanged water: 400 parts by weight The above ingredients were mixed and dissolved, and dispersed for 10 minutes using a homogenizer (IKA Ultra Turrax), to obtain a colorant particle dispersion having a median particle size of 0.16 μm and a solid content of 20% by mass.
[0169] [Toner production] <Example 1> (Preparation of core particle dispersion) Amorphous polyester resin particle dispersion (1): 40 parts Amorphous polyester resin particle dispersion (2): 40 parts Crystalline polyester resin particle dispersion: 100 parts Luminescent pigment dispersion: 500 parts Release agent particle dispersion: 60 parts Nonionic surfactant (Igepal CA897): 1.40 parts The above raw materials were placed in a 2 L cylindrical stainless steel container (diameter 30 cm) and dispersed for 10 minutes while applying shear force at 4000 rpm using a homogenizer (IKA Ultra Turrax T50). Next, 0.56 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually added dropwise, and the homogenizer was rotated at 5000 rpm for 15 minutes to obtain a raw material dispersion. Next, the raw material dispersion was transferred to a polymerization kettle equipped with a stirrer having two paddles and a thermometer, and heating was started with a mantle heater while stirring at a rotation speed of 200 rpm, and the mixture was kept at 54° C. for 2 hours to form composite core particles, thereby obtaining a composite core particle dispersion in which the composite core particles were dispersed. At this time, the pH of the dispersion was controlled to 2.2 to 3.5 with 0.3 N nitric acid and 1 N sodium hydroxide aqueous solution.
[0170] (Resin particle layer formation process) Next, 100 parts of the amorphous polyester resin particle dispersion (1) and 100 parts of the amorphous polyester resin particle dispersion (2) were added to the composite core particle dispersion, and 0.47 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to adhere the amorphous resin particles to the surfaces of the composite core particles to form a resin particle layer. The temperature was then raised to 54°C, and the mixture was kept for 0.5 hours while checking the shape and size of the composite core particles on which the resin particle layer was formed using an optical microscope and a Multisizer II (Beckman Coulter).
[0171] (Repetitive process) Next, 155 parts of the amorphous polyester resin particle dispersion (1) and 155 parts of the amorphous polyester resin particle dispersion (2) were added to the dispersion of the composite core particles in which one resin particle layer was formed, and 0.72 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to form a resin particle layer that would become the outermost layer. Next, the temperature was raised to 60°C, and the shape and size of the composite core particles in which the resin particle layer was formed were confirmed with an optical microscope and a Multisizer II (Beckman Coulter) while maintaining the mixture for 0.5 hours, thereby obtaining an aggregated particle dispersion in which aggregated particles were dispersed.
[0172] (fusion / unification process) Next, the pH was raised to 8.0, and then the temperature was raised to 80.0°C to fuse the aggregated particles, and the pH was lowered to 6.0 while maintaining the temperature at 80.0°C. After 1 hour, the heating was stopped and the mixture was cooled at a temperature drop rate of 0.1°C / min. Next, the mixture was sieved through a 20 μm mesh, repeatedly washed with water, and then dried in a vacuum dryer to obtain toner particles (1). The volume average particle size of the toner particles (1) was 10.0 μm.
[0173] The obtained toner particles (1) are toner particles in which a shell layer composed of two resin layers, an innermost layer made of an amorphous resin and an outermost layer made of an amorphous resin, is formed on the surface of a composite core particle. The total mass of the shell layer is 105 parts by mass per 100 parts by mass of the core particle, and the total thickness of the shell layer is 1.3 μm. The number of bright pigment particles contained in one composite core particle was 3.4 on average, and the content of the bright pigment relative to the entire composite core particle was 51% by mass.
[0174] (Preparation of externally added toner) 100 parts of the obtained toner particles (1) and 1.5 parts of hydrophobic silica (RY50 manufactured by Nippon Aerosil) were mixed for 2 minutes at a peripheral speed of 33 m / s using a Henschel mixer, and then sieved using a vibrating sieve with an opening of 45 μm to obtain toner (1) with external additives.
[0175] <Example 2> (Preparation of core particle dispersion) As the single core particle dispersion, the above-mentioned luster pigment dispersion was used as it was.
[0176] (Resin particle layer formation process) To 500 parts of the bright pigment dispersion, which is the single core particle dispersion, 100 parts of the amorphous polyester resin particle dispersion (1), 100 parts of the amorphous polyester resin particle dispersion (2), 60 parts of the release agent particle dispersion, and 100 parts of the crystalline polyester resin particle dispersion were added, and 0.84 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as an aggregating agent to adhere the amorphous resin particles, release agent particles, and crystalline resin particles to the surface of the single core particles to form a resin particle layer. The temperature was then raised to 54°C, and the mixture was kept for 0.5 hours while checking the shape and size of the single core particles on which the resin particle layer was formed using an optical microscope and a Multisizer II (Beckman Coulter).
[0177] (Repetitive process) Next, 195 parts of the amorphous polyester resin particle dispersion (1) and 195 parts of the amorphous polyester resin particle dispersion (2) were added to the dispersion of the single core particles on which one resin particle layer was formed, and 0.91 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to form a resin particle layer that would become the outermost layer. Next, the temperature was raised to 60°C, and the shape and size of the single core particles on which the resin particle layer was formed were confirmed using an optical microscope and a Multisizer II (Beckman Coulter) while maintaining the mixture for 0.5 hours, thereby obtaining an aggregated particle dispersion in which aggregated particles were dispersed.
[0178] (fusion / unification process) Next, the pH was raised to 8.0, and then the temperature was raised to 80.0°C to fuse the aggregated particles, and the pH was lowered to 6.0 while maintaining the temperature at 80.0°C. After 1 hour, the heating was stopped and the mixture was cooled at a temperature drop rate of 0.1°C / min. Next, the mixture was sieved through a 20 μm mesh, repeatedly washed with water, and then dried in a vacuum dryer to obtain toner particles (2). The volume average particle size of the toner particles (2) was 10.2 μm.
[0179] The obtained toner particles (2) are toner particles in which a shell layer composed of two resin layers, an innermost layer composed of an amorphous resin, a release agent, and a crystalline resin, and an outermost layer composed of an amorphous resin, is formed on the surface of a single core particle. The mass of the entire shell layer is 300 parts by mass per 100 parts by mass of the core particle, and the thickness of the entire shell layer is 1.5 μm.
[0180] (Preparation of externally added toner) Toner (2) was obtained in the same manner as toner (1), except that toner particles (2) were used instead of toner particles (1).
[0181] <Example 3> (Preparation of core particle dispersion) As the single core particle dispersion, the above-mentioned luster pigment dispersion was used as it was.
[0182] (Resin particle layer formation process) To 500 parts of the bright pigment dispersion, which is a single core particle dispersion, 90 parts of the amorphous polyester resin particle dispersion (1) and 90 parts of the amorphous polyester resin particle dispersion (2) were added, and 0.42 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to adhere the amorphous resin particles to the surface of the single core particles, forming a resin particle layer.Then, the temperature was raised to 54°C, and the shape and size of the single core particles on which the resin particle layer was formed were confirmed using an optical microscope and a Multisizer II (Beckman Coulter) while maintaining the mixture for 0.5 hours.
[0183] (Repetitive process) Next, 100 parts of the amorphous polyester resin particle dispersion (1), 100 parts of the amorphous polyester resin particle dispersion (2), and 60 parts of the release agent particle dispersion were added to the dispersion of the single core particles on which one resin particle layer was formed, and 0.61 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to form a resin particle layer that would become an intermediate layer.Then, the temperature was raised to 56°C, and the shape and size of the single core particles on which the resin particle layer was formed were confirmed using an optical microscope and a Multisizer II (Beckman Coulter) while being held for 0.5 hours. Next, 155 parts of the amorphous polyester resin particle dispersion (1) and 155 parts of the amorphous polyester resin particle dispersion (2) were added to the dispersion of the single core particles on which two resin particle layers were formed, and 0.72 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to form a resin particle layer that would become the outermost layer. Next, the temperature was raised to 58°C, and the shape and size of the single core particles on which the resin particle layers were formed were confirmed using an optical microscope and a Multisizer II (Beckman Coulter) while maintaining the temperature for 0.5 hours, thereby obtaining an aggregated particle dispersion in which aggregated particles were dispersed.
[0184] (fusion / unification process) Next, the pH was raised to 8.0, and then the temperature was raised to 80.0°C to fuse the aggregated particles. While maintaining the temperature at 80.0°C, the pH was lowered to 6.0. After 1 hour, the heating was stopped and the mixture was cooled at a temperature drop rate of 0.1°C / min. The mixture was then sieved through a 20 μm mesh, repeatedly washed with water, and dried in a vacuum dryer to obtain toner particles (3). The volume average particle size of the toner particles (3) was 10.1 μm.
[0185] The obtained toner particles (3) are toner particles in which a shell layer composed of three resin layers, that is, an innermost layer made of an amorphous resin, a middle layer made of an amorphous resin and a release agent, and an outermost layer made of an amorphous resin, is formed on the surface of a single core particle. The mass of the entire shell layer is 300 parts by mass per 100 parts by mass of the core particle, and the thickness of the entire shell layer is 1.4 μm.
[0186] (Preparation of externally added toner) Toner (3) was obtained in the same manner as toner (1), except that toner particles (3) were used instead of toner particles (1).
[0187] <Example 4> (Preparation of core particle dispersion) As the single core particle dispersion, the above-mentioned luster pigment dispersion was used as it was.
[0188] (Resin particle layer formation process) To 500 parts of the bright pigment dispersion, which is a single core particle dispersion, 90 parts of the amorphous polyester resin particle dispersion (1) and 90 parts of the amorphous polyester resin particle dispersion (2) were added, and 0.42 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to adhere the amorphous resin particles to the surface of the single core particles, forming a resin particle layer.Then, the temperature was raised to 54°C, and the shape and size of the single core particles on which the resin particle layer was formed were confirmed using an optical microscope and a Multisizer II (Beckman Coulter) while maintaining the mixture for 0.5 hours.
[0189] (Repetitive process) Next, 50 parts of amorphous polyester resin particle dispersion (1), 50 parts of amorphous polyester resin particle dispersion (2), 60 parts of release agent particle dispersion, and 100 parts of crystalline polyester resin particle dispersion were added to the dispersion of single core particles on which one resin particle layer was formed, and 0.61 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to form a resin particle layer that would become an intermediate layer.Then, the temperature was raised to 56°C, and the shape and size of the single core particles on which the resin particle layer was formed were confirmed using an optical microscope and a Multisizer II (Beckman Coulter) while being held for 0.5 hours. Next, 155 parts of the amorphous polyester resin particle dispersion (1) and 155 parts of the amorphous polyester resin particle dispersion (2) were added to the dispersion of the single core particles on which two resin particle layers were formed, and 0.72 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to form a resin particle layer that would become the outermost layer. Next, the temperature was raised to 58°C, and the shape and size of the single core particles on which the resin particle layers were formed were confirmed using an optical microscope and a Multisizer II (Beckman Coulter) while maintaining the temperature for 0.5 hours, thereby obtaining an aggregated particle dispersion in which aggregated particles were dispersed.
[0190] (fusion / unification process) Next, the pH was raised to 8.0, and then the temperature was raised to 67.5°C to fuse the aggregated particles, and while maintaining the temperature at 67.5°C, the pH was lowered to 6.0. After 1 hour, the heating was stopped and the mixture was cooled at a temperature drop rate of 0.1°C / min. The mixture was then sieved through a 20 μm mesh, repeatedly washed with water, and dried in a vacuum dryer to obtain toner particles (4). The volume average particle size of the toner particles (4) was 10.3 μm.
[0191] The obtained toner particles (4) are toner particles in which a shell layer composed of three resin layers, that is, an innermost layer made of an amorphous resin, a middle layer made of an amorphous resin, a release agent, and a crystalline resin, and an outermost layer made of an amorphous resin, is formed on the surface of a single core particle. The mass of the entire shell layer is 300 parts by mass per 100 parts by mass of the core particles, and the thickness of the entire shell layer is 1.3 μm.
[0192] (Preparation of externally added toner) Toner (4) was obtained in the same manner as toner (1), except that toner particles (4) were used instead of toner particles (1).
[0193] <Example 5> (Preparation of core particle dispersion) As the single core particle dispersion, the above-mentioned luster pigment dispersion was used as it was.
[0194] (Resin particle layer formation process) To 500 parts of the bright pigment dispersion, which is a single core particle dispersion, 90 parts of the amorphous polyester resin particle dispersion (1) and 90 parts of the amorphous polyester resin particle dispersion (2) were added, and 0.42 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to adhere the amorphous resin particles to the surface of the single core particles, forming a resin particle layer.Then, the temperature was raised to 54°C, and the shape and size of the single core particles on which the resin particle layer was formed were confirmed using an optical microscope and a Multisizer II (Beckman Coulter) while maintaining the mixture for 0.5 hours.
[0195] (Repetitive process) Next, 25 parts of amorphous polyester resin particle dispersion (1), 25 parts of amorphous polyester resin particle dispersion (2), 60 parts of release agent particle dispersion, 100 parts of crystalline polyester resin particle dispersion, and 50 parts of colorant particle dispersion were added to the dispersion of single core particles on which one resin particle layer was formed, and 0.61 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to form a resin particle layer that would become an intermediate layer. Next, the temperature was raised to 56°C, and the shape and size of the single core particles on which the resin particle layer was formed were confirmed using an optical microscope and a Multisizer II (Beckman Coulter) while being held for 0.5 hours. Next, 155 parts of the amorphous polyester resin particle dispersion (1) and 155 parts of the amorphous polyester resin particle dispersion (2) were added to the dispersion of the single core particles on which two resin particle layers were formed, and 0.72 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to form a resin particle layer that would become the outermost layer. Next, the temperature was raised to 58°C, and the shape and size of the single core particles on which the resin particle layers were formed were confirmed using an optical microscope and a Multisizer II (Beckman Coulter) while maintaining the temperature for 0.5 hours, thereby obtaining an aggregated particle dispersion in which aggregated particles were dispersed.
[0196] (fusion / unification process) Next, the pH was raised to 8.0, and then the temperature was raised to 80.0°C to fuse the aggregated particles. While maintaining the temperature at 80.0°C, the pH was lowered to 6.0. After 1 hour, the heating was stopped and the mixture was cooled at a temperature drop rate of 0.1°C / min. The mixture was then sieved through a 20 μm mesh, repeatedly washed with water, and dried in a vacuum dryer to obtain toner particles (5). The volume average particle size of the toner particles (5) was 10.2 μm.
[0197] The obtained toner particles (5) are toner particles in which a shell layer composed of three resin layers, namely, an innermost layer made of an amorphous resin, a middle layer made of an amorphous resin, a release agent, a crystalline resin, and a colorant, and an outermost layer made of an amorphous resin, is formed on the surface of a single core particle. The mass of the entire shell layer is 300 parts by mass per 100 parts by mass of the core particle, and the thickness of the entire shell layer is 1.7 μm.
[0198] (Preparation of externally added toner) Toner (5) was obtained in the same manner as toner (1), except that toner particles (5) were used instead of toner particles (1).
[0199] <Example 6> (Preparation of core particle dispersion) As the single core particle dispersion, the above-mentioned luster pigment dispersion was used as it was.
[0200] (Resin particle layer formation process) 50 parts of amorphous polyester resin particle dispersion (1) and 50 parts of amorphous polyester resin particle dispersion (2) were added to 500 parts of the glittering pigment dispersion, which is a single core particle dispersion, and 0.23 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to adhere the amorphous resin particles to the surface of the single core particles, forming a resin particle layer. The mixture was then heated to 52°C and held for 0.5 hours while checking the shape and size of the single core particles on which the resin particle layer was formed using an optical microscope and a Multisizer II (Beckman Coulter).
[0201] (Repetitive process) Next, 25 parts of amorphous polyester resin particle dispersion (1), 25 parts of amorphous polyester resin particle dispersion (2), 20 parts of release agent particle dispersion, 40 parts of crystalline polyester resin particle dispersion, and 20 parts of colorant particle dispersion were added to the dispersion of single core particles on which one resin particle layer was formed, and 0.30 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to form a resin particle layer that would become a first intermediate layer. Next, the temperature was raised to 54°C, and the shape and size of the single core particles on which the resin particle layer was formed were confirmed using an optical microscope and a Multisizer II (Beckman Coulter) while being held for 0.5 hours. Next, 40 parts of amorphous polyester resin particle dispersion (1), 40 parts of amorphous polyester resin particle dispersion (2), 40 parts of release agent particle dispersion, 60 parts of crystalline polyester resin particle dispersion, and 30 parts of colorant particle dispersion were added to the dispersion of single core particles on which two resin particle layers were formed, and 0.49 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to form a resin particle layer that would become a second intermediate layer. Next, the temperature was raised to 56°C, and the shape and size of the single core particles on which the resin particle layers were formed were confirmed using an optical microscope and a Multisizer II (Beckman Coulter) while being held for 0.5 hours. Next, 155 parts of the amorphous polyester resin particle dispersion (1) and 155 parts of the amorphous polyester resin particle dispersion (2) were added to the dispersion of the single core particles on which three resin particle layers were formed, and 0.72 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to form a resin particle layer that would become the outermost layer. Next, the temperature was raised to 58°C, and the shape and size of the single core particles on which the resin particle layers were formed were confirmed using an optical microscope and a Multisizer II (Beckman Coulter) while maintaining the temperature for 0.5 hours, thereby obtaining an aggregated particle dispersion in which aggregated particles were dispersed.
[0202] (fusion / unification process) Next, the pH was raised to 8.0, and the temperature was raised to 80·0°C to fuse the aggregated particles. While maintaining the temperature at 80·0°C, the pH was lowered to 6.0. After 1 hour, the heating was stopped and the mixture was cooled at a temperature drop rate of 0.1°C / min. The mixture was then sieved through a 20 μm mesh, repeatedly washed with water, and dried in a vacuum dryer to obtain toner particles (6). The volume average particle size of toner particles (6) was 10.1 μm.
[0203] The obtained toner particles (6) are toner particles in which a shell layer composed of four resin layers, namely, an innermost layer made of an amorphous resin, a first intermediate layer made of an amorphous resin, a release agent, a crystalline resin, and a colorant, a second intermediate layer made of an amorphous resin, a release agent, a crystalline resin, and a colorant, and an outermost layer made of an amorphous resin, is formed on the surface of a single core particle. The mass of the entire shell layer is 300 parts by mass per 100 parts by mass of the core particle, and the thickness of the entire shell layer is 1.5 μm.
[0204] (Preparation of externally added toner) Toner (6) was obtained in the same manner as toner (1), except that toner particles (6) were used instead of toner particles (1).
[0205] <Example 7> (Preparation of core particle dispersion) As the single core particle dispersion, the above-mentioned luster pigment dispersion was used as it was.
[0206] (Resin particle layer formation process) To 500 parts of the bright pigment dispersion, which is a single core particle dispersion, 90 parts of the amorphous polyester resin particle dispersion (1) and 90 parts of the amorphous polyester resin particle dispersion (2) were added, and 0.42 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to adhere the amorphous resin particles to the surface of the single core particles, forming a resin particle layer.Then, the temperature was raised to 54°C, and the shape and size of the single core particles on which the resin particle layer was formed were confirmed using an optical microscope and a Multisizer II (Beckman Coulter) while maintaining the mixture for 0.5 hours.
[0207] (Repetitive process) Next, 50 parts of amorphous polyester resin particle dispersion (1), 50 parts of amorphous polyester resin particle dispersion (2), 60 parts of release agent particle dispersion, and 100 parts of crystalline polyester resin particle dispersion were added to the dispersion of single core particles on which one resin particle layer was formed, and 0.61 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to form a resin particle layer that would become an intermediate layer.Then, the temperature was raised to 56°C, and the shape and size of the single core particles on which the resin particle layer was formed were confirmed using an optical microscope and a Multisizer II (Beckman Coulter) while being held for 0.5 hours. Next, 310 parts of amorphous polyester resin particle dispersion (3) was added to the dispersion of single core particles with two resin particle layers formed, and 0.72 parts of a 10 mass% aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to form a resin particle layer that would become the outermost layer. Next, the temperature was raised to 58°C, and the shape and size of the single core particles with the resin particle layers formed were confirmed with an optical microscope and a Multisizer II (Beckman Coulter) while maintaining the temperature for 0.5 hours, thereby obtaining an aggregated particle dispersion in which aggregated particles are dispersed.
[0208] (fusion / unification process) Next, the pH was raised to 8.0, and then the temperature was raised to 80.0°C to fuse the aggregated particles. While maintaining the temperature at 80.0°C, the pH was lowered to 6.0. After 1 hour, the heating was stopped and the mixture was cooled at a temperature drop rate of 0.1°C / min. The mixture was then sieved through a 20 μm mesh, repeatedly washed with water, and dried in a vacuum dryer to obtain toner particles (7). The volume average particle size of the toner particles (7) was 10.2 μm.
[0209] The obtained toner particles (7) are toner particles in which a shell layer composed of three resin layers, that is, an innermost layer made of an amorphous resin, a middle layer made of an amorphous resin, a release agent, and a crystalline resin, and an outermost layer made of an amorphous resin, is formed on the surface of a single core particle. The mass of the entire shell layer is 300 parts by mass per 100 parts by mass of the core particle, and the thickness of the entire shell layer is 1.3 μm.
[0210] (Preparation of externally added toner) Toner (7) was obtained in the same manner as toner (1), except that toner particles (7) were used instead of toner particles (1).
[0211] <Example 8> (Preparation of core particle dispersion) As the single core particle dispersion liquid, the light-emitting particle dispersion liquid was used as it was.
[0212] (Resin particle layer formation process) To 500 parts of the luminescent particle dispersion, which is the single core particle dispersion, 90 parts of the amorphous polyester resin particle dispersion (1) and 90 parts of the amorphous polyester resin particle dispersion (2) were added, and 0.42 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to adhere the amorphous resin particles to the surface of the single core particles, forming a resin particle layer. The mixture was then heated to 54°C and held for 0.5 hours while checking the shape and size of the single core particles on which the resin particle layer was formed using an optical microscope and a Multisizer II (Beckman Coulter).
[0213] (Repetitive process) Next, 50 parts of amorphous polyester resin particle dispersion (1), 50 parts of amorphous polyester resin particle dispersion (2), 60 parts of release agent particle dispersion, and 100 parts of crystalline polyester resin particle dispersion were added to the dispersion of single core particles on which one resin particle layer was formed, and 0.61 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to form a resin particle layer that would become an intermediate layer.Then, the temperature was raised to 56°C, and the shape and size of the single core particles on which the resin particle layer was formed were confirmed using an optical microscope and a Multisizer II (Beckman Coulter) while being held for 0.5 hours. Next, 155 parts of the amorphous polyester resin particle dispersion (1) and 155 parts of the amorphous polyester resin particle dispersion (2) were added to the dispersion of the single core particles on which two resin particle layers were formed, and 0.72 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to form a resin particle layer that would become the outermost layer. Next, the temperature was raised to 58°C, and the shape and size of the single core particles on which the resin particle layers were formed were confirmed using an optical microscope and a Multisizer II (Beckman Coulter) while maintaining the temperature for 0.5 hours, thereby obtaining an aggregated particle dispersion in which aggregated particles were dispersed.
[0214] (fusion / unification process) Next, the pH was raised to 8.0, and then the temperature was raised to 80.0°C to fuse the aggregated particles. While maintaining the temperature at 80.0°C, the pH was lowered to 6.0. After 1 hour, the heating was stopped and the mixture was cooled at a temperature drop rate of 0.1°C / min. The mixture was then sieved through a 20 μm mesh, repeatedly washed with water, and dried in a vacuum dryer to obtain toner particles (8). The volume average particle size of the toner particles (8) was 9.9 μm.
[0215] The obtained toner particles (8) are toner particles in which a shell layer composed of three resin layers, that is, an innermost layer made of an amorphous resin, a middle layer made of an amorphous resin, a release agent, and a crystalline resin, and an outermost layer made of an amorphous resin, is formed on the surface of a single core particle. The mass of the entire shell layer is 300 parts by mass per 100 parts by mass of the core particle, and the thickness of the entire shell layer is 1.1 μm.
[0216] (Preparation of externally added toner) Toner (8) was obtained in the same manner as toner (1), except that toner particles (8) were used instead of toner particles (1).
[0217] <Comparative Example 1> (Preparation of core particle dispersion) In the same manner as in Example 1, a composite core particle dispersion in which composite core particles were dispersed was obtained.
[0218] (Resin particle layer formation process) Next, 255 parts of the amorphous polyester resin particle dispersion (1) and 255 parts of the amorphous polyester resin particle dispersion (2) were added to the composite core particle dispersion, and 1.19 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as an aggregating agent to adhere the amorphous resin particles to the surfaces of the composite core particles to form a resin particle layer. Next, the temperature was raised to 58°C, and the shape and size of the composite core particles on which the resin particle layer was formed were confirmed with an optical microscope and a Multisizer II (Beckman Coulter) while maintaining the mixture for 1.0 hour, thereby obtaining an aggregated particle dispersion in which aggregated particles were dispersed.
[0219] (fusion / unification process) Next, the pH was raised to 8.0, and then the temperature was raised to 80.0°C to fuse the aggregated particles, and the pH was lowered to 6.0 while maintaining the temperature at 80.0°C. After 1 hour, the heating was stopped and the mixture was cooled at a temperature drop rate of 0.1°C / min. Next, the mixture was sieved through a 20 μm mesh, repeatedly washed with water, and then dried in a vacuum dryer to obtain toner particles (C1). The volume average particle size of the toner particles (C1) was 9.9 μm.
[0220] The toner particles (C1) thus obtained are toner particles in which a shell layer consisting of only one resin layer made of an amorphous resin is formed on the surface of a composite core particle. The mass of the entire shell layer is 105 parts by mass per 100 parts by mass of the core particle, and the thickness of the entire shell layer is 1.1 μm. The number of bright pigment particles contained in one composite core particle was 3.7 on average, and the content of the bright pigment in the entire composite core particle was 51% by mass.
[0221] (Preparation of externally added toner) A toner (C1) was obtained in the same manner as in the preparation of the toner (1), except that the toner particles (C1) were used instead of the toner particles (1).
[0222] <Comparative Example 2> (Preparation of core particle dispersion) As the single core particle dispersion, the above-mentioned luster pigment dispersion was used as it was.
[0223] (Resin particle layer formation process) To 500 parts of the bright pigment dispersion, which is a single core particle dispersion, 140 parts of the amorphous polyester resin particle dispersion (1) and 140 parts of the amorphous polyester resin particle dispersion (2) were added, and 0.65 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to adhere the amorphous resin particles to the surface of the single core particles, forming a resin particle layer.Then, the temperature was raised to 54°C, and the shape and size of the single core particles on which the resin particle layer was formed were confirmed using an optical microscope and a Multisizer II (Beckman Coulter) while maintaining the mixture for 0.5 hours.
[0224] (Repetitive process) Next, 155 parts of amorphous polyester resin particle dispersion (1), 155 parts of amorphous polyester resin particle dispersion (2), 60 parts of release agent particle dispersion, and 100 parts of crystalline polyester resin particle dispersion were added to the dispersion of single core particles with one resin particle layer formed, and 1.10 parts of a 10% by mass aqueous solution of polyaluminum chloride was gradually dropped as a flocculant to form a resin particle layer that would become the outermost layer. Next, the temperature was raised to 57°C, and the shape and size of the single core particles with the resin particle layer formed were confirmed with an optical microscope and a Multisizer II (Beckman Coulter) while maintaining for 0.5 hours, thereby obtaining an aggregated particle dispersion in which aggregated particles were dispersed.
[0225] (fusion / unification process) Next, the pH was raised to 8.0, and the temperature was raised to 80.0°C to fuse the aggregated particles. While maintaining the temperature at 80·0°C, the pH was lowered to 6.0. After 1 hour, the heating was stopped and the mixture was cooled at a rate of 0.1°C / min. The mixture was then sieved through a 20μm mesh, washed repeatedly with water, and dried in a vacuum dryer to obtain toner particles (C2). The volume average particle size of the toner particles (C2) was 10.2μm.
[0226] The toner particles (C2) thus obtained are toner particles in which a shell layer consisting of two resin layers, an innermost layer made of an amorphous resin and an outermost layer made of an amorphous resin, a release agent, and a crystalline resin, is formed on the surface of a single core particle. The mass of the entire shell layer is 300 parts by mass per 100 parts by mass of the core particle, and the thickness of the entire shell layer is 1.9 μm.
[0227] (Preparation of externally added toner) A toner (C2) was obtained in the same manner as in the preparation of the toner (1), except that the toner particles (C2) were used instead of the toner particles (1).
[0228] The configurations of the toners obtained in the above examples and comparative examples are shown in Table 1. The content (mass%) of resin particles alone relative to the entire toner obtained in the above examples and comparative examples is also shown in Table 1. In Table 1, "Composite" refers to composite core particles, "Single" refers to single core particles, "Amo" refers to amorphous resin, "WAX" refers to release agent, and "Cry" refers to crystalline resin.
[0229] [evaluation] <Preparation of carrier> 100 parts by mass of ferrite particles (manufactured by Powder Tech Co., Ltd., average particle size 50 μm) and 1.5 parts by mass of polymethyl methacrylate resin (manufactured by Mitsubishi Chemical Corporation, weight average molecular weight 95,000, the ratio of components with weight average molecular weight of 10,000 or less is 5% by mass) were placed in a pressure kneader together with 500 parts by mass of toluene, stirred and mixed at room temperature (25°C) for 15 minutes, and then heated to 70°C while mixing under reduced pressure to distill off the toluene, and then cooled and classified using a 105 μm sieve to obtain a resin-coated ferrite carrier.
[0230] <Preparation of developer> The obtained toner was mixed with a resin-coated ferrite carrier to prepare a developer having a toner concentration of 7% by mass.
[0231] <Evaluation of thin line reproducibility> A Fuji Xerox "700 Digital Color Press" was prepared, and the developer obtained in each Example and Comparative Example was filled in the developing unit. After leaving it in an environment of 5°C and 20% RH for 12 hours, 100,000 sheets of 1% print chart were formed on A4 paper in the same environment. For each of the initial (10th sheet), 1,000th, 10,000th, 50,000th, and 100,000th sheets printed, and after leaving it for 72 hours after printing 100,000 sheets, 1on1off images (images in which 1-dot lines are arranged in parallel at 1-dot intervals) with a resolution of 2,400 dpi (dot per inch) were formed as 5 cm x 5 cm charts perpendicular to the development direction at the top left, center, and bottom right of the A4 paper. The line spacing of each chart printed on the obtained sample was observed using a 100x magnifying glass with a scale to see if there were any areas that had become narrower due to toner scattering, or areas that had become wider due to thin lines becoming thinner. Based on the observation results and the line spacing of the observed areas, a grade was given according to the following criteria. The results are shown in Table 2.
[0232] -Evaluation criteria- G1: In all charts, there is no decrease in line spacing due to scattering or increase in line spacing due to thinning. G2: There is a decrease or increase in line spacing, but there is at least one chart with visible thin lines. G3: There is at least one chart where the spacing between thin lines cannot be determined or there are gaps in the thin lines. G4: There are two or more charts where the spacing between thin lines cannot be distinguished or thin lines are missing.
[0233] <Evaluation of graininess> The obtained developer was filled into a developing device of a "modified color 800 press" manufactured by Fuji Xerox Co., Ltd. After filling with the developer, it was left to stand in an environment of 35°C and 80% RH for 72 hours. Using this modified machine, in an environment of 35°C and 80% RH, a toner load of 4.0 g / m2 was applied to J paper (basis weight 82 g / m2: manufactured by Fuji Xerox Co., Ltd.). 2Patch images measuring 20 mm×20 mm were formed in 10% increments from 10% to 100% image density, and the roughness was visually evaluated according to the following criteria. The results are shown in Table 2.
[0234] -standard- G1: No noticeable graininess at all. G2: A slight sense of graininess. G3: Graininess is noticeable, but not a problem. G4: Graininess is noticeable and it feels unnatural. G5: Graininess is strongly felt.
[0235] <Evaluation of gloss unevenness> In an environment with a temperature of 28.5°C and humidity of 85%, a modified DocuCentreColor400 (manufactured by Fuji Xerox Co., Ltd.) was used to print A4-sized recording paper (manufactured by Fuji Xerox Co., Ltd., basis weight 64 g / m 2 ) an image with an image density of 100% was formed, and the 60 degree gloss was measured at 10 points using a gloss meter (BYK Micro Tri Gloss Meter (20+60+85°), manufactured by Gardner). Gloss unevenness was evaluated from the difference in gloss level (maximum value - minimum value) at the 10 points and the standard deviation. The evaluation criteria were as follows. The results are shown in Table 2.
[0236] -Evaluation criteria- G1: The difference in gloss is less than 5% and the standard deviation of 10 gloss measurements is less than 2 G2: The difference in gloss is less than 5% and the standard deviation of 10 gloss measurements is more than 2. G3: Difference in gloss is 5% or more but less than 7.5% G4: Difference in gloss is 7.5% or more and less than 10% G5: Gloss difference is 10% or more
[0237] [Table 1]
[0238] [Table 2]
[0239] From the above results, it is apparent that the toner of this embodiment has higher thin line reproducibility than the toner of the comparative example. [Explanation of symbols]
[0240] 1Y, 1M, 1C, 1K Photoconductor (an example of an image carrier) 2Y, 2M, 2C, 2K Charging roll (an example of a charging means) 3 Exposure device (an example of an electrostatic image forming means) 3Y, 3M, 3C, 3K laser beam 4Y, 4M, 4C, 4K developing device (an example of developing means) 5Y, 5M, 5C, 5K Primary transfer roll (an example of a primary transfer means) 6Y, 6M, 6C, 6K Photoconductor cleaning device (an example of a cleaning means) 8Y, 8M, 8C, 8K toner cartridges 10Y, 10M, 10C, 10K Image forming units 20 Intermediate transfer belt (an example of an intermediate transfer body) 22 Driving Roll 24 Support roll 26 Secondary transfer roll (an example of a secondary transfer means) 30 Intermediate transfer body cleaning device 107 Photoconductor (an example of an image carrier) 108 Charging roll (an example of charging means) 109 Exposure device (an example of electrostatic image forming means) 111 Developing device (an example of developing means) 112 Transfer device (an example of a transfer means) 113 Photoconductor cleaning device (an example of a cleaning means) 115 Fixing device (an example of fixing means) 116 Mounting Rail 117 Cabinet 118 Exposure Aperture 200 Process Cartridge 300 Recording paper (an example of a recording medium) P Recording paper (an example of a recording medium)
Claims
1. Core particles having a number average particle size of 1 μm or more; a shell layer which is composed of two or more resin layers containing an amorphous resin and covers a surface of the core particle, the shell layer being an outermost layer of the two or more resin layers which is composed of the amorphous resin; and wherein the toner particles have the shell layer is composed of three or more resin layers containing an amorphous resin, an innermost layer of the three or more resin layers is a resin layer made of the amorphous resin; an intermediate layer, which is a layer other than the outermost layer and the innermost layer among the three or more resin layers, includes a resin layer containing the amorphous resin and at least one selected from the group consisting of a release agent, a crystalline resin, and a colorant; The toner for developing electrostatic images, wherein the large particles include scaly particles.
2. 2. The toner for developing electrostatic images according to claim 1, wherein one of said core particles is composed of one of said large diameter particles.
3. 2. The toner for developing electrostatic images according to claim 1, wherein one of said core particles contains two or more of said large diameter particles and an amorphous resin.
4. 4. The toner for developing electrostatic images according to claim 3, wherein the content of the large diameter particles relative to the total amount of the core particles is 50% by mass or more.
5. The toner for developing electrostatic images according to any one of claims 1 to 4, wherein the toner does not contain resin particles alone that contain an amorphous resin and do not contain the large diameter particles, or the content of the resin particles alone is 80% by number or less of the entire toner for developing electrostatic images.
6. a core particle dispersion preparation step of preparing a core particle dispersion in which core particles having a number average particle size of 1 μm or more are dispersed; a resin particle layer forming step of adding amorphous resin particles to the core particle dispersion and aggregating the amorphous resin particles so as to adhere to the core particles, thereby forming a resin particle layer on the surfaces of the core particles; a repeating step of repeating the above-mentioned operation one or more times, in which the particles added in the final step are only the amorphous resin particles, thereby forming aggregated particles having two or more resin particle layers on the surface of the core particle, the outermost layer of which is made of the amorphous resin particles; a fusing / coalescing step of heating the aggregated particle dispersion in which the aggregated particles are dispersed to fuse and coalesce the aggregated particles to form toner particles; having the particles added in the resin particle layer forming step are the amorphous resin particles alone, The repeating step is a step of repeating the above operation two or more times, and the particles added in one or more of the operations excluding the last one contain the amorphous resin particles and at least one type selected from the group consisting of release agent particles, crystalline resin particles, and colorant particles, thereby forming aggregated particles having three or more resin particle layers on the surface of the core particle, an innermost layer of the three or more resin particle layers being made of the amorphous resin particles, and an intermediate layer, which is a layer other than the outermost layer and the innermost layer of the three or more resin particle layers, containing the amorphous resin particles and at least one type selected from the group consisting of the release agent particles, the crystalline resin particles, and the colorant particles, The method for producing a toner for developing an electrostatic image, wherein the large diameter particles include scaly particles.
7. 7. The method for producing a toner for developing an electrostatic image according to claim 6, wherein one of said core particles is composed of one of said large diameter particles.
8. The method for producing a toner for developing an electrostatic image according to claim 6 , wherein one of the core particles contains two or more of the large diameter particles and an amorphous resin.
9. The method for producing a toner for developing an electrostatic image according to claim 8 , wherein a content of the large diameter particles relative to the total amount of the core particles is 50% by mass or more.
10. The method for producing a toner for developing an electrostatic image according to any one of claims 6 to 9, wherein in all operations of the resin particle layer forming step and the repeating step, a coagulant is added to the core particle dispersion in addition to the amorphous resin particles.
11. The method for producing a toner for developing an electrostatic image according to any one of claims 6 to 10, wherein the aggregation temperature in each operation of the repeating steps is higher than the aggregation temperature in the operation immediately before the repeating step.
12. 12. The method for producing a toner for developing an electrostatic image according to claim 6, wherein an amount of the amorphous resin particles added in each operation of the repeating step is greater than an amount of the amorphous resin particles added in an operation immediately before the operation.
13. 6. An electrostatic image developer comprising the toner for developing electrostatic images according to claim 1.
14. The toner for developing an electrostatic image according to any one of claims 1 to 5 is contained in the container, A toner cartridge that is detachably attached to an image forming apparatus.
15. a developing unit that contains the electrostatic image developer according to claim 13 and develops an electrostatic image formed on a surface of an image carrier into a toner image by using the electrostatic image developer, A process cartridge that is detachably attached to an image forming apparatus.
16. An image carrier; a charging means for charging the surface of the image carrier; an electrostatic image forming means for forming an electrostatic image on the charged surface of the image carrier; a developing unit that contains the electrostatic image developer according to claim 13 and develops the electrostatic image formed on the surface of the image carrier into a toner image by the electrostatic image developer; a transfer means for transferring the toner image formed on the surface of the image carrier to a surface of a recording medium; a fixing means for fixing the toner image transferred onto the surface of the recording medium; An image forming apparatus comprising:
Citation Information
Patent Citations
Toner for electrostatic charge image development and manufacturing method of the same, electrostatic charge image developer, toner cartridge, process cartridge, image forming method, and image forming apparatus
JP2013072944A
Toner for electrostatic charge image development and manufacturing method of the same, electrostatic charge image developer, toner cartridge, process cartridge, image forming apparatus, and image forming method
JP2016020968A
Photoluminescent toner, electrostatic charge image developer, toner cartridge, process cartridge, image forming apparatus, and image forming method
JP2016139053A
Photoluminescent toner, electrostatic charge image developer, toner cartridge, process cartridge, image forming apparatus, and image forming method
JP2017142401A
Photoluminescent toner, electrostatic charge image developer, toner cartridge, process cartridge, image forming apparatus, and image forming method
JP2019138951A